Selbstinszenierungspraktiken als Weg zu Stärkenorientierung, Selbstbestimmung und Teilhabe – eine Kollegiale Weiterbildung für multiprofessionelle Akteursgruppen im (inklusiven) Übergang Schule-Beruf - Kundisch, Heike; Kremer, H.-Hugo; Otto, Franziska (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Der Beitrag stellt ein Qualifizierungsformat für (multi)professionelle Bildungsakteur*innen zur entwicklungsförderlichen Nutzung von Selbstinszenierungspraktiken vor. Die Konzeption und Entwicklung des Weiterbildungsformats ist im Rahmen eines Forschungs- und Entwicklungsprojekts für Jugendliche in ausbildungsvorbereitenden Bildungsgängen angesiedelt, die einen besonderen Förderbedarf im Zuge des Übergangs von der Schule in die Berufs- und Arbeitswelt aufweisen. Diese sollen durch offene und kreative Selbstdarstellungs- und Erhebungsformate dabei unterstützt werden, ihre Stärken zu erkennen, zu dokumentieren und sichtbar zu machen, sowie hierüber gleichsam für den Übergang Schule-Beruf gestärkt werden. Wir stellen zunächst den Projektrahmen vor und schärfen in diesem Kontext den Zugang über eine Grundlegung zu Selbstinszenierung sowie deren Potenziale im Kontext der inklusiven Berufsbildung und zur Stärkung der Zielgruppe. Das im Projekt entwickelte Rahmenkonzept bietet eine Orientierung zur standort- respektive bildungsgangbezogenen Anpassung und stellt damit Herausforderungen und einen entsprechenden Qualifizierungsbedarf für Bildungsakteur*innen heraus. Darauf basierend stellen wir die konzeptionellen Grundlagen, die methodische und inhaltliche Ausgestaltung zum Ansatz der ‚Kollegialen Weiterbildung‘ zur entwicklungsförderlichen Nutzung von Selbstinszenierungspraktiken vor und adressieren u. a. das Zusammenspiel von innovativer Entwicklung, Schärfung von Rollen und Kompetenzentwicklung der Bildungsakteur*innen. Abschließend diskutieren wir die konzeptionellen Entwicklungen und den Implementations- und Transferansatz. Abstract The article presents a qualification format for multi-professional actors in the educational context on the developmental use of 'Selbstinszenierungspraktiken' (which means a combination of practices for self-awareness, self-realisation and self-acceptance in a process which we are developing in our project). The concept and development of the further education format is located within the framework of a research and development project for young people with wide-ranging needs in pre-vocational education units at the transition from school to work. They will be supported in recognizing, documenting and showing their strengths through open and creative self-expression and survey formats, as well as being strengthened for the transition from school to work. First, we present the project framework and clarify the approach by a theoretical grounding of ‚Selbstinszenierung‘ (similar to a combination of self-awareness, self-realisation and self-acceptance) as well as its potentials in the context of inclusive vocational education by strengthening the target group. The developed framework provides a basis for the adaptation of the concept to a specific location or educational programme and highlights challenges and qualification needs for actors in the educational context. We present the conceptual basis, the methodological and content-related design of the collegial training approach on the developmental use of 'Selbstinszenierungspraktiken'. We address the interaction of innovative development, clarification of roles and competence development of actors in the educational context. Finally, we discuss the conceptual developments and the implementation and transfer approach.
Keywords: General Medicine

HenDi-Data (data package) v3.1.0 - Ried, Dennis; Capelle, Irmlind; Minetti, Elena; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

HenDi-Data (data package) v3.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

Jahrgangsteams zur Kooperation mit Eltern anregen – eine Aufgabe für Fortbildungen? Evaluationsergebnisse zum Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) - Grüter, Sandra; Gorges, Julia; Lütje-Klose, Birgit; Neumann, Phillip; Wild, Elke (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Für eine gelingende Umsetzung schulischer Inklusion gilt eine professionelle Weiterbildung der Lehrkräfte und des weiteren Schulpersonals als unverzichtbare Voraussetzung, um eine effektive Teamarbeit sowie die Einbindung von Eltern[i] in Erziehungs- und Bildungsprozesse zu gewährleisten. Im Projekt BiFoKi[ii] (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde eine Fortbildungsmaßnahme für inklusive Schulen entwickelt, die sowohl die intrainstitutionelle Kooperation innerhalb der Schule als auch die interinstitutionelle Zusammenarbeit mit den Eltern der Schüler*innen mit und ohne sonderpädagogischen Unterstützungsbedarf adressiert. Die Fortbildung zielt u.a. darauf ab, durch eine im Jahrgangsteam gemeinsam geplante und verantwortete Elternarbeit eine einladende Atmosphäre zu schaffen, Kommunikationswege an diverser werdende Bedarfe der Eltern und der Schüler*innen anzupassen und Eltern stärker in schulische Bildungsprozesse einzubeziehen. Zur Evaluation der Fortbildung wurde eine quasi-experimentelle Studie mit einem Prä-Post-Kontrollgruppendesign realisiert. Längsschnittliche Daten liegen für 55 Lehr- und Fachkräfte vor. Die Ergebnisse der varianzanalytischen Auswertung zeigen, dass sich die Einschätzungen zur Kooperationsbereitschaft der Eltern sowie das selbstberichtete Kooperationsverhalten im Bereich der Erziehungs- und Bildungskooperation in der Interventionsgruppe nach der Teilnahme an der Fortbildung signifikant positiver entwickelt hat als in der Kontrollgruppe. [i] Mit dem Begriff Eltern sind hier alle erziehungs- bzw. sorgeberechtigten Personen gemeint. [ii] Hinweis zur Finanzierung: Das diesem Beitrag zugrunde liegende Vorhaben BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde mit Mitteln des Bundesministeriums für Bildung und Forschung unter dem Förderkennzeichen 01NV1732in der Förderlinie „Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung“ gefördert (Projektleitung: Birgit Lütje-Klose, Elke Wild, Julia Gorges und Phillip Neumann). Abstract To implement inclusive education successfully, it is crucial that teachers and other school staff are trained to cooperate effectively as a team and to involve parents in educational processes. In the project BiFoKi (Bielefeld Training on Cooperation in inclusive), we developed an in-service training for inclusive schools that addresses the intra-institutional cooperation within schools and the inter-institutional cooperation with the parents of students with and without special educational needs. The training aims to prepare grade-level teams to create a welcoming atmosphere, adapt communication ways to the diverse needs of parents and students and to involve parents more strongly in school educational processes. To evaluate the effectiveness of the training, a quasi-experimental study with a pre-post control group design was implemented. Longitudinal data is available for 55 teachers and other professionals. The results indicate that the intervention group demonstrated a more positive development in terms of satisfaction with parents' willingness to cooperate as well as self-reported cooperative behavior in the area of educational cooperation, compared to the control group.
Keywords: General Medicine

The Demand for Voluntary Carbon Dioxide Removal – Experimental Evidence from an Afforestation Project in Germany - Bartels, Lara; Kesternich, Martin; Löschel, Andreas (Land Economics)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Governing autonomies. Imagining responsible AI in the European armament project “Future Combat Air System” - Hälterlein, Jens (The Reality of Autonomous Weapon Systems)

The Stellarium Gornergrat: Astrophysics with your own Data - Gschwind, Stéphane; Hohmann, Sascha; Müller, Andreas; Nordine, Jeffrey; Riesen, Timm-Emanuel (Journal of Physics: Conference Series)
Abstract Remote-controlled telescopes in education provide the opportunity to obtain high quality astronomy images for a broad variety of users. The Stellarium Gornergrat is such a telescope. In addition to pure observation, it offers a user-friendly interface and teaching modules so that astronomical and astrophysical projects can be integrated into everyday school life without any special prior knowledge and without requiring a lot of time. This contribution presents the Stellarium project and a provides an overview of several teaching activities.
Keywords: Computer Science Applications; History; Education

Cross-project empirical and criteria-oriented analysis of pre-service physics teachers’ pedagogical content knowledge Empirisch-kriterienorientierte Analyse des fachdidaktischen Wissens angehender Physiklehrkräfte - Zeller, Jannis; Schiering, Dustin; Kulgemeyer, Christoph; Neumann, Knut; Riese, Josef; Sorge, Stefan (Unterrichtswissenschaft)
Zusammenfassung In den letzten Jahren wurde das Professionswissen (angehender) Lehrkräfte intensiv untersucht. Neben Aussagen zur inneren Struktur liegen auch Ergebnisse über den Zusammenhang zwischen Professionswissen, Performanz in prototypischen Handlungssituationen sowie Unterrichtserfolg vor. In diesen Analysen hat sich gezeigt, dass insbesondere dem fachdidaktischen Wissen eine zentrale Rolle zukommt. Es mangelt bisher jedoch an empirisch fundierten Beschreibungen von Niveaustufen des fachdidaktischen Wissens. Zwar liegen einzelne Vorschläge vor, diese sind jedoch entweder empirisch nicht fundiert oder post hoc generiert, so dass unklar ist, inwieweit die Beschreibung der Ausprägungen auch außerhalb der jeweiligen Projektkontexte anwendbar ist. Der vorliegende Artikel stellt eine projektübergreifende Analyse des fachdidaktischen Wissens mithilfe zweier Ansätze zur Bildung von Niveaustufen vor. Dazu werden Niveaumodelle mit Daten zum fachdidaktischen Wissen aus zwei Projekten ( $$N=427$$ N = 427 und $$N=779$$ N = 779 ) mithilfe des Scale-Anchoring-Verfahrens sowie eines regressionsanalytischen Ansatzes auf Basis eines Modells hierarchischer Komplexität erstellt. Das Scale-Anchoring-Verfahren liefert Niveaubeschreibungen, die sich zwar bezüglich fachlicher und fachdidaktischer Inhalte unterschieden, aber Parallelen bezüglich lernpsychologisch interpretierbarer Operatoren zeigten. Projektübergreifend deuteten die Ergebnisse daraufhin, dass sich das fachdidaktische Wissen in niedrigen Ausprägungen auf reproduktive Aspekte beschränkt, in höheren Ausprägungen aber kreative und evaluierende Elemente hinzukommen. Das Modell hierarchischer Komplexität zeigte sich nur für einen der Datensätze als geeignet, um ein Niveaumodell abzuleiten und konnte daher für projektübergreifende Analysen nicht weiter genutzt werden. Nichtsdestotrotz lieferte die projektübergreifende Analyse mithilfe des Scale-Anchoring-Verfahrens kontextunabhängige Beschreibungen von Ausprägungen des fachdidaktischen Wissens und ermöglicht so erste Schritte in Richtung eines empirisch fundierten, inhaltlich reichhaltigen Assessments, welches über eine Einordnung mittels eines Scores hinaus geht.
Keywords: Education

HenDi-Data (data package) v4.0.0 - Ried, Dennis; Minetti, Elena; Capelle, Irmlind; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

Jahrgangsteams zur Kooperation mit Eltern anregen – eine Aufgabe für Fortbildungen? Evaluationsergebnisse zum Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) - Grüter, Sandra; Gorges, Julia; Lütje-Klose, Birgit; Neumann, Phillip; Wild, Elke (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Für eine gelingende Umsetzung schulischer Inklusion gilt eine professionelle Weiterbildung der Lehrkräfte und des weiteren Schulpersonals als unverzichtbare Voraussetzung, um eine effektive Teamarbeit sowie die Einbindung von Eltern [i] in Erziehungs- und Bildungsprozesse zu gewährleisten. Im Projekt BiFoKi [ii] (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde eine Fortbildungsmaßnahme für inklusive Schulen entwickelt, die sowohl die intrainstitutionelle Kooperation innerhalb der Schule als auch die interinstitutionelle Zusammenarbeit mit den Eltern der Schüler*innen mit und ohne sonderpädagogischen Unterstützungsbedarf adressiert. Die Fortbildung zielt u.a. darauf ab, durch eine im Jahrgangsteam gemeinsam geplante und verantwortete Elternarbeit eine einladende Atmosphäre zu schaffen, Kommunikationswege an diverser werdende Bedarfe der Eltern und der Schüler*innen anzupassen und Eltern stärker in schulische Bildungsprozesse einzubeziehen. Zur Evaluation der Fortbildung wurde eine quasi-experimentelle Studie mit einem Prä-Post-Kontrollgruppendesign realisiert. Längsschnittliche Daten liegen für 55 Lehr- und Fachkräfte vor. Die Ergebnisse der varianzanalytischen Auswertung zeigen, dass sich die Einschätzungen zur Kooperationsbereitschaft der Eltern sowie das selbstberichtete Kooperationsverhalten im Bereich der Erziehungs- und Bildungskooperation in der Interventionsgruppe nach der Teilnahme an der Fortbildung signifikant positiver entwickelt hat als in der Kontrollgruppe. [i] Mit dem Begriff Eltern sind hier alle erziehungs- bzw. sorgeberechtigten Personen gemeint. [ii] Hinweis zur Finanzierung: Das diesem Beitrag zugrunde liegende Vorhaben BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde mit Mitteln des Bundesministeriums für Bildung und Forschung unter dem Förderkennzeichen 01NV1732in der Förderlinie „Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung“ gefördert (Projektleitung: Birgit Lütje-Klose, Elke Wild, Julia Gorges und Phillip Neumann).
Keywords: Inklusion; Kooperation; Eltern; Sekundarstufe 1; Evaluation; Integration; Schulentwicklung; Elternkooperation

Concept and Implementation of a Student Design Project for the Development of Sustainable Products - Wurst, Johanna; Rosemann, Daniel; Mozgova, Iryna; Lachmayer, Roland

Evaluation of self-built low-budget particle sensors (Study Project) - Al Mamoun, Mohamed; Neukötter, Moritz

IngridKG: A FAIR Knowledge Graph of Graffiti - Sherif, Mohamed Ahmed; da Silva, Ana Alexandra Morim; Pestryakova, Svetlana; Ahmed, Abdullah Fathi; Niemann, Sven; Ngomo, Axel-Cyrille Ngonga (Scientific Data)
Abstract Graffiti is an urban phenomenon that is increasingly attracting the interest of the sciences. To the best of our knowledge, no suitable data corpora are available for systematic research until now. The Information System Graffiti in Germany project ( Ingrid ) closes this gap by dealing with graffiti image collections that have been made available to the project for public use. Within Ingrid , the graffiti images are collected, digitized and annotated. With this work, we aim to support the rapid access to a comprehensive data source on Ingrid targeted especially by researchers. In particular, we present Ingrid KG, an RDF knowledge graph of annotated graffiti, abides by the Linked Data and FAIR principles. We weekly update Ingrid KG by augmenting the new annotated graffiti to our knowledge graph. Our generation pipeline applies RDF data conversion, link discovery and data fusion approaches to the original data. The current version of Ingrid KG contains 460,640,154 triples and is linked to 3 other knowledge graphs by over 200,000 links. In our use case studies, we demonstrate the usefulness of our knowledge graph for different applications.
Keywords: Library and Information Sciences; Statistics; Probability and Uncertainty; Computer Science Applications; Education; Information Systems; Statistics and Probability

IngridKG: A FAIR Knowledge Graph of Graffiti - Sherif, Mohamed; Morim da Silva, Ana Alexandra; Pestryakova, Svetlana; Ahmed, Abdullah Fathi Ahmed; Niemann, Sven; Ngonga Ngomo, Axel-Cyrille
Graffiti is an urban phenomenon that is increasingly attracting the interest of the sciences. To the best of our knowledge, no suitable data corpora are available for systematic research until now. The Information System Graffiti in Germany project (Ingrid) closes this gap by dealing with graffiti image collections that have been made available to the project for public use. Within Ingrid, the graffiti images are collected, digitized and annotated. With this work, we aim to support the rapid access to a comprehensive data source on Ingrid targeted especially by researchers. In particular, we present IngridKG, an RDF knowledge graph of annotated graffiti, abides by the Linked Data and FAIR principles. We weekly update IngridKG by augmenting the new annotated graffiti to our knowledge graph. Our generation pipeline applies RDF data conversion, link discovery and data fusion approaches to the original data. The current version of IngridKG contains 460,640,154 triples and is linked to 3 other knowledge graphs by over 200,000 links. In our use case studies, we demonstrate the usefulness of our knowledge graph for different applications.

Lessons Learned from the Introduction of Systems Engineering - Wilke, Daria; Grothe, Robin; Bretz, Lukas; Anacker, Harald; Dumitrescu, Roman (Systems)
The introduction of Systems Engineering is an approach for dealing with the increasing complexity of products and their associated product development. Several introduction strategies are available in the literature; nevertheless, the introduction of Systems Engineering into practice still poses a great challenge to companies. Many companies have already gained experience in the introduction of Systems Engineering. Therefore, as part of the SE4OWL research project, the need to conduct a study including expert interviews and to collect the experiences of experts was identified. A total of 78 hypotheses were identified from 13 expert interviews concerning the lessons learned. Using exclusion criteria, 52 hypotheses were validated in a subsequent quantitative survey with 112 participants. Of these 52 hypotheses, 40 could be confirmed based on the survey results. Only four hypotheses were rejected, and eight could neither be confirmed nor rejected. Through this research, guidance is provided to companies to leverage best practices for the introduction of their own Systems Engineering and to avoid the poor practices of other companies.
Keywords: Information Systems and Management; Computer Networks and Communications; Modeling and Simulation; Control and Systems Engineering; Software

Venture Client Model: A systematic Literature Review - Haarmann, Lennard; Machon, Fabian; Rabe, Martin; Asmar, Laban; Dumitrescu, Roman (European Conference on Innovation and Entrepreneurship)
Established companies are increasingly opening their innovation systems to stay ahead of the competition. In this context, collaboration with innovative and agile start-ups are gaining continuously more importance. In the past established companies often used common corporate venturing methods such as incubators, accelerators, or corporate venture capital for collaboration. Compared to these methods the venture client model is relatively new and was invented by BMW employees in 2014. Using the venture client model, established companies become early clients of the start-ups even it is still a venture to do so. Together they carry out a pilot project to develop a proof of concept and validate it under real conditions. If successful, they enter a long-term collaboration to integrate the start-up’s solution into products, processes, or business models of the established company. The aim of this paper is to sum up the current literature and set a foundation for future research on this topic. Therefore, we conduct a systematic literature review. As a result, we provide a definition of the venture client model, describe characteristics, present advantages from the perspective of established companies and start-ups. In addition, we summarize the state of research regarding strategy, process, and organizational structure and for the venture client model. In terms of strategy, future research should elaborate defining elements of a strategy as well as ways to integrate the venture client model into the corporate innovation-ecosystem. Focusing on the process additional research is needed on a venture client reference process and its integration into the corporate’s core processes. Referring to the organizational structure a reference architecture for a venture client unit as well as its positioning within the organization (e.g., innovation management or corporate strategy) should be further investigated.

Evidence-based practices in teaching - Rybska, Eliza; Dudziak, Renata; Pollmeier, Pascal (Problemy Wczesnej Edukacji)
This article presents the results of the implementation of the Erasmus Plus project (KA203 financed by the European Union, contract number 2019-1-NL01-KA203-060339) Research in Teacher Education (RiTE). The aim of the project was to promote and facilitate pre-service teachers to create and undertake evidence-based practices in teaching science, technology, engineering, and mathematics (STEM). In the RiTE project, pre-service teachers were encouraged to use evidence from educational and scientific research and to experiment and introduce didactic innovations in teaching and learning processes. Although it has its justification in the tradition of thinking about science, evidence-based practice is not yet consciously applied in school practice. In the article, we present both the theoretical framework for such practices, and the results of qualitative research – an analysis of interviews conducted with students, future teachers, and novice teachers involved in the project. The presented results show changes in the context of an understanding of evidence and what evidence-based practices are in the teaching process and the vision of such teaching presented by the respondents.

Model-based Systems Engineering using Security Design Patterns in the Context of ISO/SAE 21434 - Japs, Sergej; Faheem, Faizan; Anacker, Harald; Husung, Stephan; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The development of modern vehicles is complex, especially regarding compliance with security and safety. ISO/SAE 21434 considers security and safety along the entire product life cycle. According to the standard, a system architecture, a risk analysis, and the application of countermeasures are carried out in the early system design. Design patterns are solutions to known design problems. Security Design Patterns (SDP) describe countermeasures and are used to reduce risk. After our literature review, we did not find a suitable approach that presents SDPs that would be applicable in early system design. In this paper, we present 10 SDPs for early system design, which we evaluated during an 11-week student project with 28 teams. We present the results of the quantitative analysis and the evaluation of the feedback.

Agentenbasierte Modellierung und Simulation im Pandemiemanagement - Hälterlein, Jens (TATuP - Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
Mathematical models and computer simulations play a crucial role in the context of the COVID-19 crisis for knowledge about the possible course of the pandemic and for appropriate policy decisions. The paper presents results from an ethnographic study of a government-funded R & D project dealing with agent-based modeling and simulation (ABMS) in the context of pandemic management. Based on the assumption that the use of computer simulations in pandemic management is not only a means to an end for political or epidemiological goals but also plays a significant role in determining which goals and strategies appear politically legitimate, the paper reconstructs how insights into the pandemic are generated in ABMS and specifically in the researched project and made accessible for decision-making.
Keywords: General Medicine

Umgang mit Evidenzen angehender Lehrkräfte in den Naturwissenschaften - Epistemologie in der Lehrkräfteausbildung - Pollmeier, Pascal
Eine Forderung nach evidenzbasierter Praxis (EBP) im Bildungswesen kann sowohl vor dem Hintergrund der Bedeutung wissenschaftlicher Evidenzen innerhalb gesellschaftlicher Diskurse als auch der Evidenzbasierung in anderen Bereichen formuliert werden. Der Umgang mit und die Bewertung von Evidenzen stellen somit vor dem Hintergrund epistemologischer Überzeugungen relevante Aufgaben für den Chemieunterricht dar. Dabei ist unklar, inwiefern (angehende) Lehrkräfte über Kompetenzen in EBP verfügen. Bestehende Studien weisen auf einen Bedarf der fachdidaktischen Analyse und Förderung von Kompetenzen in EBP bei angehenden Lehrkräften hin.Im Rahmen dieser Dissertation wurde die Domänenspezifität der Kompetenzen in EBP sowie deren Förderung in einem fachdidaktischen Kontext untersucht. Dabei wurde ein weiterer Schwerpunkt auf den Umgang mit anomalen Beobachtungen im Sinne widersprüchlicher Evidenzen gelegt. Innerhalb von drei Teilstudien wurden unterschiedliche methodische Zugänge zur Kompetenz in EBP auf Grundlage epistemologischer Überzeugungen gewählt.Die Ergebnisse weisen auf einen Förderbedarf der Kompetenz in EBP für angehende Lehrkräfte aller Unterrichtsfächer hin. Eine entwickelte Intervention für angehende Chemielehrkräfte weist eine Wirksamkeit zur Förderung von Kompetenzen in EBP auf. Im Rahmen einer Modellierungsstudie kann der Einfluss von Fachwissen sowie Indizien für einen Einfluss epistemologischer Überzeugungen auf den Umgang mit anomalen Beobachtungen gezeigt werden.
Keywords: Epistemologie; Evidenzen; evidence-based practice

Mosaic Tiles: Comparative Theological Hermeneutics and Christian-Jewish Dialogue About the Land - Ackermann, Domenik (CrossCurrents)
Keywords: General Engineering

SAFE -Streaming approaches for Europe - Enhancing the digital competences by streaming approaches for schools to tackle the challenges of COVID-19. The Teacher-Training-Platform on the SAFE Project Website - Schneider, Jennifer Nicole

Green-4-Future – Project Insights to its best! In: Training and Cooperation Activity (TCA) “Green Erasmus: pathways to sustainable projects and institutions” - Schneider, Jennifer Nicole

STEMinAction- Final Project Meeting – Unlocking Long-Term Sustainability: Harnessing Open Educational Resources (OER) Beyond Project Lifetimes - Schneider, Jennifer Nicole

Multiobjective Optimization of Non-Smooth PDE-Constrained Problems - Bernreuther, Marco; Dellnitz, Michael; Gebken, Bennet; Müller, Georg; Peitz, Sebastian; Sonntag, Konstantin; Volkwein, Stefan (arXiv:2308.01113)
Multiobjective optimization plays an increasingly important role in modern applications, where several criteria are often of equal importance. The task in multiobjective optimization and multiobjective optimal control is therefore to compute the set of optimal compromises (the Pareto set) between the conflicting objectives. The advances in algorithms and the increasing interest in Pareto-optimal solutions have led to a wide range of new applications related to optimal and feedback control - potentially with non-smoothness both on the level of the objectives or in the system dynamics. This results in new challenges such as dealing with expensive models (e.g., governed by partial differential equations (PDEs)) and developing dedicated algorithms handling the non-smoothness. Since in contrast to single-objective optimization, the Pareto set generally consists of an infinite number of solutions, the computational effort can quickly become challenging, which is particularly problematic when the objectives are costly to evaluate or when a solution has to be presented very quickly. This article gives an overview of recent developments in the field of multiobjective optimization of non-smooth PDE-constrained problems. In particular we report on the advances achieved within Project 2 "Multiobjective Optimization of Non-Smooth PDE-Constrained Problems - Switches, State Constraints and Model Order Reduction" of the DFG Priority Programm 1962 "Non-smooth and Complementarity-based Distributed Parameter Systems: Simulation and Hierarchical Optimization".

Approach for a Safety Element out of Context for an Actuator Circuit Control Module - Noun, H.; Mozgova, Iryna; Abdelfattah, M.; Zeller, G.; Rajesh, G.; Lachmayer, R. (International Journal of Industrial and Manufacturing Engineering)
Several modules in automotive are usually modified and adapted for various project-specific applications. Due to a standardized safety concept a high reusability is accessible. A safety element out of context (SEooC) according to ISO 26262 can be a suitable approach. Based on the same safety concept and analysis, common modules can reach high reusability. For developing according to a module out of context, an appropriate and detailed development approach is required. This paper shows how to deduce this development processes for platform modules. Therefore, the detailed approach of the SEooC is derived. The aim is to create a detailed workflow for all phases of the development and integration of any kind of system modules. As an application example, an automotive project for an actuator control module is considered.

HenDi-Data (data package) v2.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

HenDi-Data (data package) v1.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

A new strategic approach for R&D project portfolio selection using efficiency-uncertainty maps - Namazi, Mehdi; Tavana, Madjid; Mohammadi, Emran; Bonyadi Naeini, Ali (Benchmarking: An International Journal)
Purpose New business practices and the globalization of markets force firms to take innovation as the fundamental pillar of their competitive strategy. Research and Development (R&D) plays a vital role in innovation. As technology advances and product life cycles become shorter, firms rely on R&D as a strategy to invigorate innovation. R&D project portfolio selection is a complex and challenging task. Despite the management's efforts to implement the best project portfolio selection practices, many projects continue to fail or miss their target. The problem is that selecting R&D projects requires a deep understanding of strategic vision and technical capabilities. However, many decision-makers lack technological insight or strategic vision. This article aims to provide a method to capitalize on the expertise of R&D professionals to assist managers in making informed and effective decisions. It also provides a framework for aligning the portfolio of R&D projects with the organizational vision and mission. Design/methodology/approach This article proposes a new strategic approach for R&D project portfolio selection using efficiency-uncertainty maps. Findings The proposed strategy plane helps decision-makers align R&D project portfolios with their strategies to combine a strategic view and numerical analysis in this research. The proposed strategy plane consists of four areas: Exploitation Zone, Challenge Zone, Desperation Zone and Discretion Zone. Mapping the project into this strategic plane would help decision-makers align their project portfolio according to the corporate perspectives. Originality/value The new approach combines the efficiency and uncertainty dimensions in portfolio selection into an integrated framework that: (i) provides a complete representation of the stochastic decision-making processes, (ii) models the endogenous uncertainty inherent in the project selection process and (iii) proposes a computationally practical and visually unique solution procedure for classifying desirable and undesirable R&D projects.
Keywords: Business and International Management; Strategy and Management

Designing digital actor engagement platforms for local high streets: an action design research study - Bartelheimer, Christian; zur Heiden, Philipp; Berendes, Carsten Ingo; Beverungen, Daniel (European Journal of Information Systems)
High streets across Europe continue to lose consumers to online retail, leading to business closures and the decline of city centres, impairing cities’ overall liveability. To counter this vicious cycle, our study presents smartmarket2, the first instantiation of a digital actor engagement platform designed specifically for high streets. smartmarket2 enables hybrid online-offline customer journeys by connecting consumers to stores and other high street service providers. In an action design research (ADR) project, we design, implement and evaluate smartmarket2, involving 150 high street operators and 2,300 citizens in three cycles of building, intervention and evaluation. We derive four design principles that contribute prescriptive knowledge on the design of digital actor engagement platforms. Our results reveal that such a platform is able to increase engagement, but that it is subject to actors’ engagement dispositions.
Keywords: Digital platform; action design research; design principles; actor engagement; engagement platform; location-based advertising

A PLACE FOR A DATA SCIENCE PROJECT IN SCHOOL: BETWEEN STATISTICS AND EPISTEMIC PROGRAMMING - PODWORNY, SUSANNE; Hüsing, Sven; SCHULTE, CARSTEN (STATISTICS EDUCATION RESEARCH JOURNAL)
Aspects of data science surround us in many contexts, for example regarding climate change, air pollution, and other environmental issues. To open the “data-science-black-box” for lower secondary school students we developed a data science project focussing on the analysis of self-collected environmental data. We embed this project in computer science education, which enables us to use a new knowledge-based programming approach for the data analysis within Jupyter Notebooks and the programming language Python. In this paper, we evaluate the second cycle of this project which took place in a ninth-grade computer science class. In particular, we present how the students coped with the professional tool of Jupyter Notebooks for doing statistical investigations and which insights they gained.
Keywords: Education; Statistics and Probability

Proaktives Management von Anforderungsänderungen in der Entwicklung komplexer technischer Systeme - Oleff, Christian
Anforderungsänderungen sind ein wesentlicher Grund für Ineffizienzen und Projektfehlschläge in der Entwicklung komplexer technischer Systeme. Proaktives Management von Anforderungsänderungen hat das Potenzial, den Umgang mit Anforderungsänderungen effizienter zu gestalten. Dafür ist ein systematischer Ansatz erforderlich, der eine ganzheitliche Bewertung und Handhabung des Änderungsrisikos im industriellen Entwicklungskontext ermöglicht. Im Rahmen dieser Dissertation wird mit der ProMaRC-Methodik ein neuartiger Ansatz für das proaktive Management von Anforderungsänderungen vorgestellt. Die Methodik wurde in enger Zusammenarbeit mit Industrieanwender:innen aus der Automobilindustrie entwickelt und anhand von fünf Fallstudien validiert. Mittels automatisierter Abhängigkeitsanalyse auf Grundlage künstlicher Intelligenz wird der Anwendungsaufwand gegenüber bestehenden Ansätzen reduziert. Die teilautomatisierte Bewertung und Handhabung der Änderungswahrscheinlichkeit und -auswirkung erfolgt anhand eines modifizierten PageRank-Algorithmus und umfasst erstmalig alle für die Risikoanalyse relevanten Einflussfaktoren. Die Validierung belegt, dass durch die ProMaRC-Methodik eine überzeugende Kombination aus praxistauglichem Anwendungsaufwand und Vollständigkeit der Analyse erzielt wird. Damit erschließt diese Dissertation das bisher kaum beachtete Forschungsfeld des proaktiven Managements von Anforderungsänderungen und fördert eine effizientere Produktentwicklung.

The Scale4Edge RISC-V Ecosystem - Ecker, Wolfgang; Adelt, Peer; Müller, Wolfgang; Heckmann, Reinhold; Krstic, Milos; Herdt, Vladimir; Drechsler, Rolf; Angst, Gerhard; Wimmer, Ralf; Mauderer, Andreas; Stahl, Rafael; Emrich, Karsten; et al. (In Proceedings of the Design Automation and Test Conference and Exhibition (DATE 2022))
This paper introduces the project Scale4Edge. The project is focused on enabling an effective RISC-V ecosystem for optimization of edge applications. We describe the basic components of this ecosystem and introduce the envisioned demonstrators, which will be used in their evaluation.

Who has the future in mind? Gender, time perspectives, and pro-environmental behaviour - Hoffmann, Christin; Hoppe, Julia Amelie; Ziemann, Niklas (Environmental Research Letters)
Abstract An individual’s relation to time may be an important driver of pro-environmental behaviour. We studied whether young individual’s gender and time-orientation are associated with pro-environmental behaviour. In a controlled laboratory environment with students in Germany, participants earned money by performing a real-effort task and were then offered the opportunity to invest their money into an environmental project that supports climate protection. Afterwards, we controlled for their time-orientation. In this consequential behavioural setting, we find that males who scored higher on future-negative orientation showed significantly more pro-environmental behaviour compared to females who scored higher on future-negative orientation and males who scored lower on future-negative orientation. Interestingly, our results are completely reversed when it comes to past-positive orientation. These findings have practical implications regarding the most appropriate way to address individuals in order to achieve more pro-environmental behaviour.
Keywords: Public Health; Environmental and Occupational Health; General Environmental Science; Renewable Energy; Sustainability and the Environment

Performance Management Approach for Digital Platforms in B2B Markets - Özcan, Leon; Kirchberg, Lisa; Koldewey, Christian; Dumitrescu, Roman (The Role of Innovation: Past, Present, Future)
Digital platforms have already led to disruptions in multiple B2C markets and are becoming increasingly dominant in B2B markets. As a result, more and more companies are trying to participate in the platform economy. However, the successful development and operation of a digital platform is associated with significant challenges, which leads to 85% of all platforms failing. A core challenge is the dynamic nature of the platform economy, with varying strategic objectives at different stages in the platform lifecycle. Platform operators must continuously monitor platform progress and adjust their strategy. Utilizing action research in the real-world platform project AI Marketplace, we developed a lifecycle-oriented performance management approach for digital platforms in B2B markets. It enables platform operators to reflect on their position in the platform lifecycle, derive relevant strategic objectives, and monitor them with suitable key performance indicators. Hence, allowing them to secure the long-term success of their platform business.
Keywords: Digital Platform; Two-Sided Market; Multi-Sided Market; Platform Lifecycle; Platform Monitoring; Performance Management

Comparing Student high and low Reading Performance with Differentiated Digital Reading Materials - Paleczek, Lisa; Ender, Daniela; Kogler, Andrea; Seifert, Susanne (European Conference on e-Learning)
The present study investigates eight Grade-4 classes (9- to 12-year-olds, 52.1% girls) who worked on at least 10 lessons using project RegioDiff material. The study focuses on one of these lessons (including nine text passages and corresponding tasks) and on students with low (19 students, percentile <15) and high reading skills (29 students, percentile > 70). While students were working with the material, screencasts were recorded (30h). The construct “task performance” (processing time, response accuracy, and task engagement) was then analysed using the screencasts.
The analysis revealed that the two groups differed significantly in the processing time of two tasks, but not in the total time spent on all nine tasks. Significant differences were revealed also for general task engagement. Task engagement was highly correlated with processing time. Participants with higher reading skills spent more time on the tasks and were more engaged than participants with lower reading skills. However, we did not find any differences in terms of answer accuracy. This indicates that task difficulty and student reading skills were well matched.
The study also shows how tasks may be adapted or augmented in order to match the learning environment more closely to student learning needs.

Responsibility Assignment in Systems Engineering - Gräßler, Iris; Thiele, Henrik; Grewe, Benedikt; Hieb, Michael (Proceedings of the Design Society)
Abstract Increasing system complexity can be controlled by using systems engineering processes. INCOSE defines processes with inputs and outputs (artifacts) for this purpose. Specific SE roles are used to organize the tasks of the processes within the company. In this work, the responsibilities for artifacts are evaluated by means of the RACI scheme and examined by a cluster analysis and discussed for a SE transformation project with a German automotive OEM. As a result of the study, the optimal composition for systems engineering teams is identified and the systems engineering roles are prioritized.
Keywords: systems engineering (SE); project management; model-based systems engineering (MBSE)

Supporting Geometry Learning Digitally-an Interdisciplinary Project to Foster Spatial Competences and Individual Learning Paths by Using Adaptable Algorithmic Feedback Capabilities - Winkelnkemper, Felix; Huhmann, Tobias; Bechinie, Dominik; Eilerts, Katja; Lenke, Michael; Schulte, Carsten (Society for Information Technology & Teacher Education International Conference)
Keywords: ⛔ No DOI found

How to enable pre-service teachers to design technological teaching and learning inclusively? – On the nature and consideration of basic needs in teacher training - Schröer, Franz; Tenberge, Claudia (PATT39 - PATT on the Edge Technology, Innovation and Education)
Theoretical approaches to the transformation towards an inclusive educational system in Germany mostly agree on the involvement of developmental tasks in subject related research (Hinz, 2011). The common understanding of inclusion as a process geared towards equal participation of all children (Booth, 2012) requires a reflexive questioning of established values, attitudes and practices in order to develop inclusive subject related research, teacher training and teaching and learning (Pech & Schomaker, 2013). Among other things, this results in consequences for the design of pre- service teacher training. To a large extent, teacher education is driven by the promotion of central competencies, interests and self-efficacy (Baumert & Kunter, 2011). It aims towards the development and realisation of inclusive interdisciplinary science and social studies (‘Sachunterricht’) in primary education (Moser, 2018). In conjunction with largely acknowledged constructivist approaches to teaching and learning (Möller, 2001), the development of personality, the consideration of basic needs (Deci & Ryan, 1993) and promotion of individual potentials are repeatedly fundamentally represented in subject related and pedagogical considerations (Feuser, 1989; GDSU, 2013). Therefore, the aforementioned constructivist approach is connected to several certain key paradigms for teaching and learning processes (e.g., Vygotskij, 1978; Posner et al., 1982; van de Pol et al., 2010). In this regard, the nature of primary school students’ basic needs have empirically not been sufficiently studied yet. Theoretical frameworks from motivational psychology (Deci & Ryan, 1993) do not explicitly address how individual needs differ and how the diversity of needs can be included in joint-learning, multi-perspective technology education classes. The research project the present paper is part of aims to develop a research-based concept for the professionalisation of pre-service teachers in a seminar course. Therefore, the promotion of the pre- service teachers’ interests and self-efficacy expectations have been assessed in a pre-post research design with a control group visiting another course not related to technology education and inclusion. The present paper describes and discusses first results of the project and will give an outlook on subsequent developmental tasks.
Keywords: Inclusion; basic needs; pre-service teacher training; interest; self-efficacy

Computational Essays as an Approach for Reproducible Data Analysis in lower Secondary School - Hüsing, Sven; Podworny, Susanne (Proceedings of the IASE 2021 Satellite Conference)
Data Science has become an increasingly important aspect of our everyday lives as we gain a lot of different insights from data analyses, for example in the context of environmental issues. In order to make the process of data analyses comprehensible for lower secondary school students, we developed a data analysis project for computer science classes, focusing on gaining insights from environmental data by using the concept of epistemic programming. In this article, we report on the second implementation of this project, which was conducted in a ninth-grade computer science class. Concretely, we want to examine, how far the students were able to create computational essays to conduct reproducible data analyses on their own. In this regard, the computational essays created with the help of the professional tool Jupyter Notebooks will be examined in terms of aspects of reproducibility.

Situational Development of Low-Code Applications in Manufacturing Companies - Kirchhoff, Jonas; Weidmann, Nils; Sauer, Stefan; Engels, Gregor (Proceedings of the 25th International Conference on Model Driven Engineering Languages and Systems: Companion Proceedings)
Companies show an increasing interest in low-code development platforms to facilitate application development by domain experts without sophisticated software development knowledge. Thus, companies aim for a more efficient development of more effective applications since domain experts as so-called citizen developers are no longer limited by the availability and domain knowledge of trained software developers. Nevertheless, efficiency and effectiveness of application development is traditionally also largely influenced by the use of a suitable software development method. Domain experts are, however, not trained in software development methods. This introduces a risk of domain experts creating unusable applications or exceeding the designated time frame of a project (or both). In this paper, we therefore propose an initial version of a situational software development method which supports domain experts in manufacturing companies during the low-code development of applications. The method can be tailored based on situational factors, considering application requirements, features of the used low-code development platform, and characteristics of the development team. We also present feedback corroborating the usefulness of our method and future extension points based on expert interviews.

Automated Requirement Dependency Analysis for Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Hieb, Michael; Preuß, Daniel (Proceedings of the Design Society)
Abstract Requirements changes are a leading cause for project failures. Due to propagation effects, change management requires dependency analysis. Existing approaches have shortcomings regarding ability to process large requirement sets, availability of required data, differentiation of propagation behavior and consideration of higher order dependencies. This paper introduces a new method for advanced requirement dependency analysis based on machine learning. Evaluation proves applicability and high performance by means of a case example, 4 development projects and 3 workshops with industry experts.

Innovative Online Measurement and Modelling Approach for Property-Controlled Flow Forming Processes - Kersting, Lukas; Arian, Bahman; Vasquez, Julian Rozo; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (Key Engineering Materials)
The production of complex multi-functional, high-strength parts is becoming increasingly important in the industry. Especially with small batch size, the incremental flow forming processes can be advantageous. The production of parts with complex geometry and locally graded material properties currently depicts a great challenge in the flow forming process. At this point, the usage of closed-loop control for the shape and properties could be a feasible new solution. The overall aim in this project is to establish an intelligent closed-loop control system for the wall thickness as well as the α’-martensite content of AISI 304L-workpieces in a flow forming process. To reach this goal, a novel sensor concept for online measurements of the wall thickness reduction and the martensite content during forming process is proposed. It includes the setup of a modified flow forming machine and the integration of the sensor system in the machine control. Additionally, a simulation model for the flow forming process is presented which describes the forming process with regard to the plastic workpiece deformation, the induced α’-martensite fraction, and the sensor behavior. This model was used for designing a closed-loop process control of the wall thickness reduction that was subsequently realized at the real plant including online measured feedback from the sensor system.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Knowledge Base Enhanced & User-centric Dialogue Design for OTF Computing - Ahmed, Mobeen
This thesis aims to provide a bidirectional chatbot solution for the requirement engineering process. The Sonderforschungsbereich (SFB) 901 intends to provide the composition of software service On-the-Fly (OTF). The sub-project (B1) of the SFB 901 project deals with the parameters of service configuration. OTF Computing aims to eradicate the dependency on the requirement engineers for the software development process. However, there is no existing bidirectional chatbot solution that analyses user software requirements and provides viable suggestions to the user regarding their service. Previously, CORDULA chatbot was developed to analyze the software requirements but cannot keep the conversation’s context. The Rasa framework is integrated with the knowledge base to solve the issue, the knowledge base provides domain-specific knowledge to the chatbot. The software description is passed through the natural language understanding process to give consciousness to the chatbot. This process involves various machine learning models, including app family classification, to correctly identify the domain for user OTF service. The statistical models like naïve Bayes, kNN and SVM are compared with transformer models for this classification task. Furthermore, the entities (functional requirements) are also separated from the user description. The chatbot provides the suggestion of requirements from the preliminary service template with the support of the knowledge base. Furthermore, the generated response is compared with the state-of-the-art DialoGPT transformer model and ChatterBot conversational library. These models are trained over the software development related conversational dataset. All the responses are ranked using the DialoRPT model, and the BLEU score to evaluates the models’ responses. Moreover, the chatbot mod- els are tested with human participants, they used and scored the chatbot responses based on effectiveness, efficiency and satisfaction. The overall response accuracy is also measured by averaging the user approval over the generated responses.

Proactive Management of Requirement Changes in the Development of Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Preuß, Daniel (Applied Sciences)
Requirement changes and cascading effects of change propagation are major sources of inefficiencies in product development and increase the risk of project failure. Proactive change management of requirement changes yields the potential to handle such changes efficiently. A systematic approach is required for proactive change management to assess and reduce the risk of a requirement change with appropriate effort in industrial application. Within the paper at hand, a novel method for Proactive Management of Requirement Changes (ProMaRC) is presented. It is developed in close collaboration with industry experts and evaluated based on workshops, pilot users’ feedback, three industrial case studies from the automotive industry and five development projects from research. To limit the application effort, an automated approach for dependency analysis based on the machine learning technique BERT and semi-automated assessment of change likelihood and impact using a modified PageRank algorithm is developed. Applying the method, the risks of requirement changes are assessed systematically and reduced by means of proactive change measures. Evaluation shows high performance of dependency analysis and confirms the applicability and usefulness of the method. This contribution opens up the research space of proactive risk management for requirement changes which is currently almost unexploited. It enables more efficient product development.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Powder Spread Process Monitoring in Polymer Laser Sintering and its Influences on Part Properties - Klippstein, Sven Helge; Heiny, Florian; Pashikanti,, Nagaraju; Gessler, Monika; Schmid, Hans-Joachim (JOM - The Journal of The Minerals, Metals & Materials Society (TMS))
Confidence in additive manufacturing technologies is directly related to the predictability of part properties, which is influenced by several factors. To gain confidence, online process monitoring with dedicated and reliable feedback is desirable for every process. In this project, a powder bed monitoring system was developed as a retrofit solution for the EOS P3 laser sintering machines. A high-resolution camera records each layer, which is analyzed by a Region-Based Convolutional Neural Network (Mask R-CNN). Over 2500 images were annotated and classified to train the network in detecting defects in the powder bed at a very high level. Each defect is checked for intersection with exposure areas. To distinguish between acceptable imperfections and critical defects that lead to part rejection, the impact of these imperfections on part properties is investigated.

Fortschrittskontrolle der Modellierung mechatronischer Produkte - Gräßler, Iris; Wiechel, Dominik; Thiele, Henrik (Tagungsband der Fachtagung VDI-Mechatronik)
Die Anforderungen an die Entwicklung mechatronischer Systeme sind seit der Erstfassung der VDI Richtlinie 2206 im Jahr 2004 stetig gestiegen. Nach einer umfassenden Überarbeitung ist 2021 die Richtline im Weißdruck neu veröffentlicht worden. Neben dem Systemdenken als gestärktes Kernelement des V-Modells und sechs Kontrollpunkten nur Gliederung der sachlogischen Aufgaben ist die durchgängig explizite „Modellierung und Analyse“ eine wesentliche Neuerung der Richtlinie. Da sich die Kontrollfragen nur auf den Entwicklungsprozess im Ganzen beziehen, wird durch die Betrachtung der Modellierung eines Batteriesystems aus einem Entwicklungsprojekt eines deutschen Automobilherstellers die folgende Forschungsfrage betrachtet: Welche spezifischen Kontrollfragen zu Fortschritt und Reifegrad der Modellierung eines Batteriesystems können aus den Kontrollpunkten des V-Modells (VDI 2206:2020) gefolgert werden? Als Ergebnis der Forschung liegen hinsichtlich der Modellierung eines spezifischen Systems detaillierte Kontrollfragen vor, die eine methodische Unterstützung für die modellbasierte Systementwicklung komplexer mechatronischer Systeme bieten. Zusätzlich ermöglichen sie der Projektleitung die Überprüfung des aktuellen Status der Entwicklung und sichern die Vollständigkeit des Systemmodells ab.

Model-Based Effect-Chain Analysis for Complex Systems - Gräßler, Iris; Wiechel, Dominik; Koch, Anna-Sophie; Preuß, Daniel; Oleff, Christian (Proceedings of the Design Society)
Abstract Effect chain modeling approaches are applied to model cause-effect relations and analyze affected elements and dependencies. In this paper a systematic literature research is conducted to derive main characteristics and limitations of existing approaches. Then, the Model-based Effect Chain Analysis (MECA) method is introduced. Evaluation proves applicability of the method by means of a case example. This is done in the context of a project with a German automotive company. In the project 66 workshops were conducted to model certification-compliant effect chains in accordance to the UN ECE 156.

Einfluss der Berufserfahrung von Multiplikatorinnen und Multiplikatoren auf die Wirksamkeit von Fortbildungsmaßnahmen zur frühen mathematischen Bildung. Zeitschrift Für Erziehungswissenschaft - Hagena, Maike; Bruns, Julia; Gasteiger, Hedwig (Zeitschrift für Erziehungswissenschaft)
Teachers expect facilitators to have own teaching experience as a teacher in order to be able to carry out effective teacher professional development programs. As part of the project EmMa(M), it is investigated, to which extent the teaching experience of facilitators influences the development of early childhood teachers' (n = 83) mathematical pedagogical content knowledge (MPCK) and early childhood teachers' enjoyment of mathematics in the context of a teacher professional development program. It turns out that the teaching experience of the facilitators has no influence on the development of early childhood teachers' MPCK, but favors the development of early childhood teachers' enjoyment of mathematics. Controlling for this increased enjoyment an influence of teaching experience on the development of early childhood teachers' MPCK emerges, but in favor of the participating facilitators who have no teaching experience but have a university degree.
Keywords: Facilitator professional development; Early childhood teachers; Teaching; experience; Early mathematics education

Citizen Social Science in Germany—cooperation beyond invited and uninvited participation - Göbel, Claudia; Mauermeister, Sylvi; Henke, Justus (Humanities and Social Sciences Communications)
Abstract This article presents an overview of characteristics of Citizen Social Science (CSS) in Germany. CSS is defined as scientific research in the humanities and social sciences, carried out in cooperation between professional and non-professional researchers. The study draws on an online survey and semi-structured interviews with project coordinators and co-researchers. It finds that participatory research activities in the humanities and social sciences are very diverse in their disciplinary traditions and organisational settings. Key features of CSS activities initiated inside as well as outside academic institutions are analysed to understand patterns of participation and cooperation. The results show that CSS activities are frequently realised in heterogeneous consortia of academic and non-academic partners. These consortia influence interactions between professional and non-professional researchers. To investigate these observations further, the article extends the analytical gaze from participation of individual volunteers to various forms of cooperation in consortia. This shift in attention brings to sight additional actors and activities that are usually not, or only marginally, considered in discussions about C(S)S. Staff of civil society organisations, municipalities, schools or cross-sectoral initiatives as well as university students are involved in making CSS work. In addition to research tasks, CSS rests on science communication, project management and intermediation activities. This extended perspective captures more diverse constellations of knowledge production in participatory research in the social sciences and humanities than the common focus on participation. In this way, the article aims to lay the groundwork for understanding the functioning of CSS beyond aspects described by the concept of invited and uninvited participation. It shows that CSS activities are not limited to capacitating lay people for participation in science. A more adequate description is that such projects are concerned with facilitating cooperation with co-researchers and other partners in consortia inside and outside of academia. On this basis, the article introduces the notion of cooperation capacity as a heuristic device to propose new prompts for research on CSS as well as for supporting CSS practice.
Keywords: General Economics; Econometrics and Finance; General Psychology; General Social Sciences; General Arts and Humanities; General Business; Management and Accounting

A PLACE FOR A DATA SCIENCE PROJECT IN SCHOOL: BETWEEN STATISTICS AND EPISTEMIC PROGRAMMING - PODWORNY, SUSANNE; HÜSING, SVEN; SCHULTE, CARSTEN (STATISTICS EDUCATION RESEARCH JOURNAL)
Aspects of data science surround us in many contexts, for example regarding climate change, air pollution, and other environmental issues. To open the “data-science-black-box” for lower secondary school students we developed a data science project focussing on the analysis of self-collected environmental data. We embed this project in computer science education, which enables us to use a new knowledge-based programming approach for the data analysis within Jupyter Notebooks and the programming language Python. In this paper, we evaluate the second cycle of this project which took place in a ninth-grade computer science class. In particular, we present how the students coped with the professional tool of Jupyter Notebooks for doing statistical investigations and which insights they gained.
Keywords: Education; Statistics and Probability

EU-CERT. First Transnational Project Meeting. Presentation at the EU-CERT Meeting: Financial, Marketing and Dissemination. - Schneider, Jennifer Nicole

Von der Axiomatik bis zur Schnittstellenaufgabe: Entwicklung und Erforschung eines ganzheitlichen Lehrkonzepts für eine Veranstaltung Geometrie für Lehramtsstudierende - Hoffmann, Max
Vorgestellt wird ein Entwicklungsforschungsprojekt zur Konzeption und Durchführung einer Veranstaltung "Geometrie für Lehramtsstudierende". Die Schwerpunkte des Projekts sind zum einen die inhaltliche Gestaltung der Veranstaltung und zum anderen die Umsetzung von Professionsorientierung. Bezogen auf den inhaltlichen Aufbau wird das auf metrischen Räumen aufbauende Axiomensystem der "Saccheri-Ebene" vorgestellt und mit alternativen axiomatischen Zugängen zur ebenen Geometrie verglichen. Die Frage nach der Umsetzung von Professionsorientierung in Fachveranstaltungen ist eng mit der Problematik der zweiten Diskontinuität verbunden. In der Arbeit wird dieses Problem auf Grundlage der Synthese von theoretischen Hintergründen zur Bedeutung von mathematischem Wissen und Können für professionelle Handlungskompetenz von Mathematiklehrkräften diskutiert und darauf aufbauend werden theoriebasierte Entwurfsprinzipien für professionsorientierte Fachveranstaltungen entworfen. Zentrale Elemente der methodischen Gestaltung sind die sogenannten "Schnittstellenwochen" zu den Themen Kongruenz und Symmetrie sowie das begleitende Schnittstellen-ePortfolio. Das zentrale Ergebnis der Arbeit ist ein theoretisch fundiertes und empirisch evaluiertes ganzheitliches Veranstaltungskonzept für eine professionsorientierte Geometrie-Veranstaltung für Lehramtsstudierende, dessen Konzeption auf andere Fachveranstaltungen übertragbar ist. Darüber hinaus ergeben sich im Rahmen der durchgeführten Entwicklungsforschung verschiedene neue Beiträge zur Geometriedidaktik in Schule- und Hochschule.

European Certificates and Accreditation for European Projects. The EU-CERT-Project – Insight into PR1: EU-CERT - Research on Quality Criteria, Accreditation and Certificate Structures - Beutner, Marc; Schneider, Jennifer Nicole

EU-CERT - European Certificates and Accreditation for European Projects. The EU-CERT-Project - Insight into PR2: EU-CERT - Concept Design for Accreditation and Certification Processes - Beutner, Marc; Schneider, Jennifer Nicole

EU-CERT - European Certificates and Accreditation for European Projects. The EU-CERT-Project - Insight into PR4: EU-CERT - Accreditation Handbook - Beutner, Marc; Schneider, Jennifer Nicole

EU-CERT. Second Transnational Project Meeting.Presentation about accreditation and certificate structures - Schneider, Jennifer Nicole

E-Learning, Digitisation and Units for Learning at VET schools Creating Online Learning Environments in Technical Education for European metal industry. New Opportunities and Challenges for European VET schools in metal industry. Insights in the EDU VET Project

EU-CERT - European Certificates and Accreditation for European Projects. The EU-CERT – Accreditation Conference. Current Status of the EU-CERT project - Schneider, Jennifer Nicole

EU-CERT - European Certificates and Accreditation for European Projects. The EU-CERT-Project - Dissemination and Exploitation - Beutner, Marc; Schneider, Jennifer Nicole

Scaffolding Close Reading of Mathematical Text in Pre-service Primary Teacher Education at the Tertiary Level: Design and Evaluation - Rezat, Sebastian; Malik, Sara Naseem; Leifeld, Markus (International Journal of Science and Mathematics Education)
Abstract Even in the digital age, learning mathematics at an academic level still requires much reading of mathematical text. Research has shown that reading mathematical text requires readers to engage with all the structures of the book and with its pedagogical voice, making connections, and plausible reasoning. Specific practices and strategies that support the close reading of mathematical text have been suggested; however, descriptions and empirical evaluations of materials designed to support these activities are rare. We present the design and first evaluation cycle of materials developed in a design research project that aims to scaffold close reading of mathematical text. The materials were designed and evaluated in a German university course on elementary geometry for first-year teacher education students who study mathematics to become primary teachers. The reading strategies were explained and modeled for students in reading-strategy videos. Additionally, close reading of mathematical text was scaffolded by close-reading tasks and homework tasks and problems that build on the reading strategies and were specifically designed to foster understanding of the mathematical text. Survey data were collected from 296 students to evaluate their use of and attitude toward the different materials. The quantitative results indicate that students used the materials and were generally able to learn the course content by themselves. From all provided materials, they found the close-reading tasks most helpful. A qualitative analysis of answers to open questions revealed issues with different materials, particularly with the script, and requests for additional materials. The issues with the script were categorized inductively. The categories are presented as a qualitative result of the study and discussed.
Keywords: General Mathematics; Education

Civic Statistics for Prospective Teachers: Developing Content and Pedagogical Content Knowledge Through Project Work - Podworny, Susanne; Frischemeier, Daniel; Biehler, Rolf (Statistics for Empowerment and Social Engagement)

Mechanisches Fügen von FKV-FKV-Verbindungen - Han, Daxin; Meschut, Gerson
Within the scope of the research project, four new mechanical joining processes for the singlestage, pre-hole-free joining of FRP-FRP joints were further developed. For this purpose, the joining processes under consideration were first implemented on existing equipment at the research institute. Based on the successful adaptation of the joining processes, characteristics of the joints were documented by means of micrographs and observation of external characteristics, on the basis of which measures for process modification were derived. The process modifications were carried out on a process-specific basis for a selected GFRPGFRP joint. The aim was to improve the joint quality, in particular with regard to the reduction of laminate damage, by means of targeted element and tool development in addition to the increase in process stability. Based on these results, a realistic suitability evaluation of the joining methods was carried out with regard to process and manufacturing flexibility. As a result, two self-piercing riveting processes, which showed the greatest suitability potential, were examined in more detail to analyse the application limits. In the process, the joints were sampled on further material combinations with varied fibre and matrix systems. In addition, joints with adhesive were investigated, in which the influence of the adhesive viscosity on the joint properties was analysed. The joint properties of the new joining method were then comprehensively determined by tensile tests under quasi-static, cyclic loads. Finally, the behaviour of the optimised joints under corrosive load was characterised in the salt spray test. Through the targeted process modifications in this project, the FRP-FRP joints can be joined with less damage, enabling improved joint quality in the FRP-based components.

Situation-specific Business Model Development Methods for Mobile App Developers - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Enterprise, Business-Process and Information Systems Modeling)
The development of effective business models is an essential task in highly competitive markets like mobile ecosystems. Existing development methods for these business models do not specifically focus that the development process profoundly depends on the situation (e.g., market size, regulations) of the mobile app developer. Here, a mismatch between method and situation can lead to poor resource management and longer development cycles. In software engineering, situational method engineering is used for software projects to configure a development method out of a method repository based on the project situation. Analogously, we support creating situation-specific business model development methods with a method base and new user roles. Here, the method engineer obtains the knowledge of the domain expert and stores it in the method base as elements, building blocks, and patterns. The expert knowledge is derived from a grey literature review on mobile development processes. After this, the method engineer constructs the development method based on the described situation of the business developer. We provide an open-source tool and evaluate it by constructing a local event platform's business model development method.
Keywords: Business Model Development; Situational Method Engineering; Mobile App; Business Model Development Tools

Holistic change propagation and impact analysis in requirements management - Gräßler, Iris; Oleff, Christian; Preuß, Daniel
In developing complex technical systems, requirements are subject to continuous change. Systematic and holistic change impact analysis and proactive measures are required for reducing the number of requirement changes and their negative impact. There is no method to analyse the holistic impact of a requirement change in the context of developing complex technical systems. Holistic analysis requires to consider the local effects of requirement changes as well as effects from change propagation. To develop an approach for holistic change propagation and impact analysis, twelve performance goals are defined. Those are derived from a state of research analysis as well as an industry workshop. A three-step method is proposed. Firstly, requirement dependencies that cause change propagation are detected. Secondly, critical requirements are automatically identified based on a Page Rank algorithm. Thirdly, change impact of critical requirements is analysed based on a guideline. Validation proves that ten goals are fulfilled and two are partly fulfilled. The method addresses major shortcomings of preceding research and enables sound decision making for development engineers both before a change occurs and during decision process on a change request. This helps to reduce negative change impact in development projects and the risk of project failure.

PROJECT FOR THE DEVELOPMENT OF OPERATIONAL AND DEMAND-ORIENTED FIREFIGHTING EQUIPMENT - Hanses, Hendrik; Horwath, Ilona (Book of Abstracts 37th Danubia Adria Symposium on Advances in Experimental Mechanics)

Constructing the “Competent” Pupil: Optimizing Human Futures Through Testing? - Dahmen, Stephan (Social Inclusion)
In the last decade, the German transition system has witnessed the large‐scale introduction of so‐called “analysis of potentials” (Potenzialanalysen) in secondary compulsory schooling. In most German Länder, 8th graders must participate in a two‐day assessment center which combines psychometric testing with observations of their social and professional competencies in pre‐specified tasks. The programmatic aim of these assessments is to “introduce pupils early to choosing a job” (Bundesministerium für Bildung und Forschung [BMBF], 2017, p. 2) as well as to enhance the propensity of pupils to “take responsibility for their own future” (BMBF, 2017, p. 9). In the context of the German school‐to‐work system, the introduction of these new forms of diagnostics bear witness to a new preventive political rationality that aims at reducing the entry age into upper secondary education, reduce the recourse to so‐called “transition measures” and optimizing transitions into an apprenticeship market that is characterized by structural inequalities and “mismatch” between pupils’ job aspirations and the offers in apprenticeship places. However, little is known on the role of competency testing devices for the construction of further trajectories and aspirations and their role in the reproduction of inequalities in transitions from school to work. Based on an in‐depth analysis of policy documents and competency profiles (the documents handed out to the pupils after undergoing testing), the article reconstructs the political rationale for the introduction of the so‐called Potenzialanalysen. Based on a Foucauldian framework, we show how pupils are constructed as “competent” subjects. We show that competency assessments are part and parcel of a political rationality that aims at the promotion of a specific (future‐oriented, optimized, self‐regulated) relation to one’s own biographical future on the side of the pupils. Our results demonstrate that competency profiles construct the process of choosing a job as an individualized project of the self and that they invisibilize structural barriers and power relations. In doing so, competency assessments potentially contribute to the reproduction of inequalities in post‐secondary education through delegating “cooling out” processes from institutional gatekeepers to the interiority of persons.
Keywords: Sociology and Political Science; Social Psychology

Technological and Inclusive Education - Considering Students’ Needs Towards Technological Learning in Primary Schools - Schröer, Franz; Tenberge, Claudia (TECHNE SERIES - Forskning i slöjdpedagogik och slöjdvetenskap)
Research on technological educationininterdisciplinary scienceand socialstudies (Sachunterricht) in German primary schools emphasizes that childrenare generally interested in technology. While several STEAM initiatives point towards a growing recognition of technological literacy, the consideration of technology education ininterdisciplinaryscience and social studies is quite underrepresented in practice as well as in research and teacher training.Takinginto accountthe UN-CRPDclaims foran inclusive educational system andthus alsothe right to equally participate in a free society,participation in society through participation in technological development is a fundamental common goal of technological and inclusive education and part of widely recognized technological literacy.It is therefore not well understood how teaching and learning arrangementscan consider and satisfythe needs of all different students. The research project the present paper is part of tries to unveil the appearance of student’s basic needs in relation to technological educationfor all children. Thisinitial quantitative part of a grounded theory study examined the subjective significance of basic psychological needs in interdisciplinary science studies in primary educationto allow for a well-reasoned sample choice for subsequent interviews. Quantitative results point towards some revisions regarding the instrument used and several implications on the diversity of students ́needs in science and social studies. Future research is needed with larger samples for factor-analysis.
Keywords: Inclusion; basic needs; Technology Education; Primary Education; autonomy; competence; social relatedness

Chancen des inklusionsorientierten Sachunterrichts für didaktisch-diagnostisches Handeln. Konzeptionelle und methodologisch-methodische Grundlagen eines forschungsbasierten Entwicklungsansatzes für die Lehrer*innenbildung - Schroeder, René; Blumberg, Eva; Kottmann, Brigitte; Miller, Susanne; Reh, Anne (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
In der Herausforderung Unterricht inklusionsbezogen weiterzuentwickeln, manifestiert sich unter anderem die Forderung nach der Qualifizierung von (angehenden) Lehrkräften bzgl. der Anwendung und Umsetzung einer alltagsintegrierten Diagnostik mit dem Ziel, Kinder individualisiert und gleichzeitig mit Bezug auf einen gemeinsamen Lerngegenstand zu unterrichten. Dabei ist ein didaktisch-diagnostisches Handeln aller Lehrkräfte gefordert, welches im Kontext einer professionellen und inklusionsorientierten Gestaltung sowie einer angemessenen Begleitung und Förderung von Lern- und Entwicklungsprozessen steht. In der Konzeption entsprechender Aus- und Weiterbildungsformate setzt das geplante Projekt DiPoSa (Didaktisch-diagnostische Potentiale des inklusionsorientierten Sachunterrichts) an. Ziel ist es durch einen Design-Based-Research-Ansatz (DBR) Videovignetten zu erstellen und zu evaluieren, mittels derer entsprechende Kompetenzen von (angehenden) Lehrkräften im Sachunterricht weiterentwickelt werden können. Dabei bietet insbesondere der Sachunterricht als vielperspektivisches Integrationsfach der Grundschule einen passenden Rahmen, kindliche Lernpotentiale als Ausgangspunkt für didaktisch-diagnostisches Handeln nutzbar zu machen. Denn in aktuellen inklusionsorientierten Ansätzen des Sachunterrichts sind sowohl reformpädagogisch orientierte als auch offene Konzepte und Modelle des adaptiven Unterrichts zu finden, die sich an den unterschiedlichen Programmatiken der Umsetzung von individueller Förderung orientieren. Im folgenden Beitrag werden die dem geplanten Projekt zugrundeliegenden theoretischen und empirischen Zugänge erläutert und die forschungsmethodische Umsetzung durch einen DBR-Ansatz als methodologische Basis für eine Theorie-Praxis-verzahnende Forschungsperspektive auf diagnostisches Handeln sowie die Förderung diagnostischer Handlungskompetenzen durch Videovignetten im Kontext der Aus- und Weiterbildung von (Sachunterrichts-)Lehrkräften diskutiert. Abstract The challenge to further promote practices of inclusive teaching, requires the development of assessment literacy. Combined with the aim to teach all children in a collaborative learning environment, qualification of teachers (in training) in the application and implementation of formative assessment as an integrated daily routine is needed. Therefore, the project DiPoSa focuses on the development of appropriate training and qualification formats. The project heads to create and evaluate video vignettes using a design-based-research approach (DBR), which can then be used to further develop assessment literacy of teachers in social studies and science in primary education. As a multi-perspective integrative subject in elementary school social studies and science in primary education offers a suitable framework for practices of formative assessment taking children's learning potentials as a serious concern. Foundations can be seen in current inclusive approaches to social studies and science in primary education, where reform pedagogically orientation and open concepts can as well be found as models of adaptive teaching. Although there are different theoretical and programmatic implementations, both perspectives share an orientation towards individual support of children. With this in mind the following article tries to lay down the theoretical and empirical approaches of the planed project DiPoSa and discusses methodological foundations of the project. The discussion focuses on how assessment practices as well as assessment literacy can be promoted through a DBR research-design using video vignettes in the context of teacher education and qualification and rooting in a deepened science-practice partnership.Zusammenfassung englisch
Keywords: General Medicine

Chancen des inklusionsorientierten Sachunterrichts für didaktisch-diagnostisches Handeln. Konzeptionelle und methodologisch-methodische Grundlagen eines forschungsbasierten Entwicklungsansatzes für die Lehrer*innenbildung - Schroeder, René; Blumberg, Eva; Kottmann, Brigitte; Miller, Susanne; Reh, Anne (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
In der Herausforderung Unterricht inklusionsbezogen weiterzuentwickeln, manifestiert sich unter anderem die Forderung nach der Qualifizierung von (angehenden) Lehrkräften bzgl. der Anwendung und Umsetzung einer alltagsintegrierten Diagnostik mit dem Ziel, Kinder individualisiert und gleichzeitig mit Bezug auf einen gemeinsamen Lerngegenstand zu unterrichten. Dabei ist ein didaktisch-diagnostisches Handeln aller Lehrkräfte gefordert, welches im Kontext einer professionellen und inklusionsorientierten Gestaltung sowie einer angemessenen Begleitung und Förderung von Lern- und Entwicklungsprozessen steht. In der Konzeption entsprechender Aus- und Weiterbildungsformate setzt das geplante Projekt DiPoSa (Didaktisch-diagnostische Potentiale des inklusionsorientierten Sachunterrichts) an. Ziel ist es durch einen Design-Based-Research-Ansatz (DBR) Videovignetten zu erstellen und zu evaluieren, mittels derer entsprechende Kompetenzen von (angehenden) Lehrkräften im Sachunterricht weiterentwickelt werden können. Dabei bietet insbesondere der Sachunterricht als vielperspektivisches Integrationsfach der Grundschule einen passenden Rahmen, kindliche Lernpotentiale als Ausgangspunkt für didaktisch-diagnostisches Handeln nutzbar zu machen. Denn in aktuellen inklusionsorientierten Ansätzen des Sachunterrichts sind sowohl reformpädagogisch orientierte als auch offene Konzepte und Modelle des adaptiven Unterrichts zu finden, die sich an den unterschiedlichen Programmatiken der Umsetzung von individueller Förderung orientieren. Im folgenden Beitrag werden die dem geplanten Projekt zugrundeliegenden theoretischen und empirischen Zugänge erläutert und die forschungsmethodische Umsetzung durch einen DBR-Ansatz als methodologische Basis für eine Theorie-Praxis-verzahnende Forschungsperspektive auf diagnostisches Handeln sowie die Förderung diagnostischer Handlungskompetenzen durch Videovignetten im Kontext der Aus- und Weiterbildung von (Sachunterrichts-)Lehrkräften diskutiert. Abstract The challenge to further promote practices of inclusive teaching, requires the development of assessment literacy. Combined with the aim to teach all children in a collaborative learning environment, qualification of teachers (in training) in the application and implementation of formative assessment as an integrated daily routine is needed. Therefore, the project DiPoSa focuses on the development of appropriate training and qualification formats. The project heads to create and evaluate video vignettes using a design-based-research approach (DBR), which can then be used to further develop assessment literacy of teachers in social studies and science in primary education. As a multi-perspective integrative subject in elementary school social studies and science in primary education offers a suitable framework for practices of formative assessment taking children's learning potentials as a serious concern. Foundations can be seen in current inclusive approaches to social studies and science in primary education, where reform pedagogically orientation and open concepts can as well be found as models of adaptive teaching. Although there are different theoretical and programmatic implementations, both perspectives share an orientation towards individual support of children. With this in mind the following article tries to lay down the theoretical and empirical approaches of the planed project DiPoSa and discusses methodological foundations of the project. The discussion focuses on how assessment practices as well as assessment literacy can be promoted through a DBR research-design using video vignettes in the context of teacher education and qualification and rooting in a deepened science-practice partnership.Zusammenfassung englisch

Berufsspezifische Reflexionsprozesse durch Einzelfallarbeit im Projekt „Schule für alle": Analyse von zwei Praxisberichten mittels der Dokumentarischen Methode - Reh, Anne; Kottmann, Brigitte; Miller, Susanne (QfI - Qualifizierung für Inklusion)
In dem Beitrag wird ausgehend von der Notwendigkeit einer inklusionspädagogischen Professionalisierung im Lehramtsstudium ein erziehungswissenschaftliches Projekt dargestellt, das es den teilnehmenden Bachelor-Studierenden in besonderer Weise ermöglicht, berufsspezifische Reflexionsprozesse zu durchlaufen. In dem Projekt übernehmen Studierende die einjährige pädagogische Förderung von Grundschulkindern mit bildungsrelevanten Benachteiligungsfaktoren, die häufig von Selektionspraktiken und -maßnahmen bedroht sind. Die Bearbeitung von vorliegenden Common-Sense-Theorien im inklusiven Kontext gilt dabei als ein relevantes Professionalisierungsziel in der Lehramtsausbildung. Konkret werden Ausschnitte aus Praktikumsberichten von zwei Studierenden mittels der dokumentarischen Methode ausgewertet und einander gegenübergestellt, um daran herauszuarbeiten, inwiefern sich die Reflexionen unterscheiden. Es zeigt sich anhand der Analysen, dass im Rahmen der Praxisphase eine Reflection-on-Action und auch die vertiefte Reflexion eigener Common-Sense-Theorien grundsätzlich möglich, jedoch nicht voraussetzungslos ist. Insbesondere kann auch anhand der gewählten Einzelfälle verdeutlicht werden, wie individuell inklusionsbezogene Professionalisierungsprozesse im Rahmen der vorliegenden Praxisphase verlaufen können. Die Analyse offenbart multiple Professionalisierungschancen in Abhängigkeit von den Rahmenbedingungen des Projekts, den individuellen Schwerpunkten der pädagogischen Arbeit oder den individuellen Reflexionen der Studierenden. Abstract Based on the necessity of an inclusive pedagogical professionalisation in the teacher training program, this article presents an educational science project that enables the participating Bachelor students in a unique manner to go through profession-specific reflection processes. In the project, students take on the one-year pedagogical support of primary school children with educational disadvantage factors, who are often threatened by selection practices and measures. In this context, working through present common-sense theories in an inclusive context is considered a relevant professionalization goal in teacher education. Specifically, excerpts from internship reports of two students are analysed by means of the documentary method and compared to each other in order to work out the extent to which the reflections differ. The analyses show that reflection-on-action and in-depth reflection on one's own common-sense theories are generally possible during the practical phase, but not without preconditions. In particular, the selected individual cases can be used to illustrate how individual inclusion-related professionalisation processes can take place within the framework of the present practical phase. The analysis reveals multiple opportunities for professionalisation depending on the general framework of the project, the individual focal points of the pedagogical work or the individual reflections of the students.

Forming of metastable austenitic stainless steel tubes with axially graded martensite content by flow-forming - Arian, Bahman; Homberg, Werner; Riepold, Markus; Trächtler, Ansgar; Rozo Vasquez, Julian; Walther, Frank
One of the main objectives of production engineering is to reproducibly manufacture (complex) defect-free parts. To achieve this, it is necessary to employ an appropriate process or tool design. While this will generally prove successful, it cannot, however, offset stochastic defects with local variations in material properties. Closed-loop process control represents a promising approach for a solution in this context. The state of the art involves using this approach to control geometric parameters such as a length. So far, no research or applications have been conducted with closed-loop control for microstructure and product properties. In the project on which this paper is based, the local martensite content of parts is to be adjusted in a highly precise and reproducible manner. The forming process employed is a special, property-controlled flow-forming process. A model-based controller is thus to generate corresponding correction values for the tool-path geometry and tool-path velocity on the basis of online martensite content measurements. For the controller model, it is planned to use a special process or microstructure (correlation) model. The planned paper not only describes the experimental setup but also presents results of initial experimental investigations for subsequent use in the closed-loop control of α’-martensite content during flow-forming.
Keywords: Flow-forming; Spinning; Process Strategy; Martensite Content; Property Control; Micromagnetic Measurement; Metastable Austenitic Stainless Steel

Aufgaben und Zuständigkeiten von allgemeinen und sonderpädagogischen Lehrkräften sowie Fachkräften der Schulsozialarbeit in inklusiven Schulen der Sekundarstufe I. Erste Ergebnisse aus dem BiFoKi-Projekt - Neumann, Phillip; Grüter, Sandra; Eckel, Lisa; Lütje-Klose, Birgit; Wild, Elke; Gorges, Julia (Zeitschrift für Heilpädagogik)
Multiprofessionelle Teams sind notwendiger Bestandteil inklusiver Schulen. Die Verteilung von Aufgaben, welche über die Zusammenarbeit von allgemeinen und sonderpädagogischen Lehrkräften im Unterricht hinausgehen, wurde bislang jedoch selten systematisch untersucht. Im Beitrag werden deskriptive Befunde aus dem Projekt BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) zu den Zuständigkeiten von allgemeinen (N = 170) und sonderpädagogischen Lehrkräften (N = 24) sowie Schulsozialarbeiterinnen (N = 11) an inklusiven Sekundar- und Gesamtschulen präsentiert. Sie deuten auf eine Persistenz traditioneller Rollenmuster und Aufgabenverteilungen hin. Bei den befragten sonderpädagogischen Lehrkräften können zwei unterschiedliche Rollenmuster herausgearbeitet werden. Die Schulsozialarbeiterinnen weisen ein enges Arbeitsfeld mit einem Fokus auf Eltern-Schule-Kooperation auf.
Keywords: Inklusion; Sonderpädagogik; Sekundarstufe; Gesamtschulen; Kooperation; Schulsozialarbeit; BiFoKi

V-model based development of cyber-physical systems and cyber-physical production systems - Gräßler, Iris; Wiechel, Dominik; Roesmann, Daniel; Thiele, Henrik (Procedia CIRP)
Challenges of the development of mechatronic systems and corresponding production systems have increased steadily. Changes are primarily due to increased product complexity and the connection to the internet of things and services, enabling Cyber-Physical Systems (CPS) and Cyber-Physical Production Systems (CPPS). Major innovations of the revised VDI guideline 2206 for developing mechatronic systems are systems thinking as a core element and six checkpoints for structuring deliverables along the V-Model. These checkpoints serve for orientation in result progress and thus enable a structured and complete development process. However, tasks and checkpoints of the new guideline focus on the product development itself without integrating the development of related CPPS, enabling optimization simultaneously to system development. Implications are derived by a three-step analysis. The paper at hand contributes fundamental extensions of the checkpoint questions regarding integrated CPPS development. These questions provide methodical support for system developers of CPPS for CPS by enabling the project manager to check the status, schedule further development steps and evaluate the maturity of the whole, integrated development.
Keywords: Cyber-Physical Production System (CPPS); V-Model; Product System Development; Integrated Development; VDI 2206

Selbstreguliertes Lernen im berufsschulischen Übergangssystem - Daniel-Söltenfuß, Desiree; Schwabl, Franziska (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

A first introduction to data science education in secondary schools: Teaching and learning about data exploration with CODAP using survey data - Frischemeier, Daniel; Biehler, Rolf; Podworny, Susanne; Budde, Lea (Teaching Statistics)
Abstract In this paper, we will describe an introduction to Data Science for secondary school students. We will report on the design and implementation of an introductory unit on “Data and data detectives with CODAP” in which secondary school students used the online tool CODAP to explore real and meaningful survey data on leisure time activities and media use (so‐called JIM‐PB data) in a statistical project setting as a starting point for data science. The JIM‐PB data set served as a valuable data set that offered meaningful and exciting opportunities for data exploration for secondary school students, and CODAP proved to be a valuable tool for the first explorations of this data.
Keywords: Education; Statistics and Probability

Digital transformation in industry - Schneider, Jennifer Nicole (Fostering Digitisation and Industry 4.0: Education – Vocation - Industry – Future. New Opportunities and Challenges for European VET. Insights in the DigI-VET Project)

Teaching and Learning Materials - Schneider, Jennifer (Fostering Digitisation and Industry 4.0: Education – Vocation - Industry – Future. New Opportunities and Challenges for European VET. Insights in the DigI-VET Project)

Technology-centred learning processes as digital artistic development: On the reciprocal effects of conceptual models, metaphors and presets - Neuhausen, Timo; Wernicke, Carsten; Ahlers, Michael (Journal of Music, Technology & Education)
This case study looks at a self-directed learning process of a professional classical-trained musician adopting a previously unknown digital-material musical device. In order to achieve the desired artistic result, the musician has to modify his music-related action in favour of the device’s calls for action, which are shown to him by a preset session. For this purpose, a specific interface relation must be established in the connection between the user and the device. The case study is contrasted with data from its framing research project. Findings include aspects as affirmation or degrees of unfamiliarity and their respective impacts on the subject’s action repertoires. A model of learning in the context of digital media or interfaces is introduced and discussed. It offers a specific potential for identifying particularities of how meaning and functionality of digital-material musical devices are embedded into everyday artistic contexts.
Keywords: Music; Education; Music Technology

Du Châtelet on Sufficient Reason and Empirical Explanation - Wells, Aaron (The Southern Journal of Philosophy)
Abstract For Émilie Du Châtelet, I argue, a central role of the principle of sufficient reason is to discriminate between better and worse explanations. Her principle of sufficient reason does not play this role for just any conceivable intellect: it specifically enables understanding for minds like ours. She develops this idea in terms of two criteria for the success of our explanations: “understanding how” and “understanding why.” These criteria can respectively be connected to the determinateness and contrastivity of explanations. The crucial role Du Châtelet’s principle of sufficient reason plays in identifying good explanations is often overlooked in the literature, or else run together with questions about the justification and likelihood of explanations. An auxiliary goal of the article is to situate Du Châtelet’s principle of sufficient reason with respect to some of the general epistemological and metaphysical commitments of her Institutions de Physique , clarifying how it fits into the broader project of that work.
Keywords: Philosophy

Digitalisation in the Classroom – Learning Tools - Schneider, Jennifer Nicole (Fostering Digitisation and Industry 4.0: Education – Vocation - Industry – Future. New Opportunities and Challenges for European VET. Insights in the DigI-VET Project)

Fostering Digitisation and Industry 4.0: Education – Vocation – Industry – Future. New Opportunities and Challenges for European VET. Insight in the DigI-VET Project

Digital diversity across Europe. Policy brief September 2021 of Working Package 2 'Mapping digital transformations across Europe' in Horizon-2020-Project DigiGen - Ayllón, Sara; Casamassima, Gianna; Drossel, Kerstin; Eickelmann, Birgit; Hyggen, Christer; Lado, Samuel; Port, Sonja; Broekstra, Nienke

Work-related practices of local managers of live music events in Ostwestfalen-Lippe (OWL) and their impact on cultural participation - Flath, Beate; Momen Pour Tafreshi, Maryam (Arts and the Market)
Purpose The purpose of this article is to illuminate the relations of work-related practices of local managers of live music events in Ostwestfalen-Lippe (OWL) and barriers and needs of vulnerable customers (VC) in order to explore possibilities to increase cultural participation of VC. Design/methodology/approach This article explores work-related practices of managers of live music events in OWL and asks if and to what extent these practices have an influence on the cultural participation of “vulnerable customers” (VC). It combines the findings of two studies: a) an explorative investigation on the work-related self-conceptions of managers of live music events in OWL (Study 1), and b) a sub-project on cultural participation of VC, which is part of the research project “kulturPreis. Increasing cultural participation through innovative and economically sustainable pricing concepts”, funded by the German Federal Ministry of Education and Research (Study 2). Findings It can be stated that there is an imbalance of knowledge: while VC tend to have a clear understanding of which barriers are the responsibility of managers of live music events, managers tend to lack knowledge regarding the needs of VC, and regarding the interrelationships between financial and social barriers facing them. Whether this knowledge and understanding can be developed in the future depends on the possibilities of exchanges between managers of live music events, cultural institutions, welfare organisations, political institutions and not least VC. Originality/value Based on these studies, this article combines different approaches by linking work-related practices of managers of live music events with cultural participation of VC.

Disordered crystals from first principles II: Transport coefficients - Kühne, Thomas; Heske, Julian Joachim; Prodan, Emil (Annals of Physics)
This is the second part of a project on the foundations of first-principle calculations of the electron transport in crystals at finite temperatures, aiming at a predictive first-principles platform that combines ab-initio molecular dynamics (AIMD) and a finite-temperature Kubo-formula with dissipation for thermally disordered crystalline phases. The latter are encoded in an ergodic dynamical system (Ω,G,dP), where Ω is the configuration space of the atomic degrees of freedom, G is the space group acting on Ω and dP is the ergodic Gibbs measure relative to the G-action. We first demonstrate how to pass from the continuum Kohn–Sham theory to a discrete atomic-orbitals based formalism without breaking the covariance of the physical observables w.r.t. (Ω,G,dP). Then we show how to implement the Kubo-formula, investigate its self-averaging property and derive an optimal finite-volume approximation for it. We also describe a numerical innovation that made possible AIMD simulations with longer orbits and elaborate on the details of our simulations. Lastly, we present numerical results on the transport coefficients of crystal silicon at different temperatures.

A Discrete and Continuous Study of the Max-Chain-Formation Problem – Slow Down to Speed Up - Castenow, Jannik; Kling, Peter; Knollmann, Till; Meyer auf der Heide, Friedhelm (Stabilization, Safety, and Security of Distributed Systems - 22nd International Symposium, SSS 2020, Austin, Texas, USA, November 18-21, 2020, Proceedings)
Most existing robot formation problems seek a target formation of a certain minimal and, thus, efficient structure. Examples include the Gathering and the Chain-Formation problem. In this work, we study formation problems that try to reach a maximal structure, supporting for example an efficient coverage in exploration scenarios. A recent example is the NASA Shapeshifter project, which describes how the robots form a relay chain along which gathered data from extraterrestrial cave explorations may be sent to a home base. As a first step towards understanding such maximization tasks, we introduce and study the Max-Chain-Formation problem, where $n$ robots are ordered along a winding, potentially self-intersecting chain and must form a connected, straight line of maximal length connecting its two endpoints. We propose and analyze strategies in a discrete and in a continuous time model. In the discrete case, we give a complete analysis if all robots are initially collinear, showing that the worst-case time to reach an $\varepsilon$-approximation is upper bounded by $\mathcal{O}(n^2 \cdot \log (n/\varepsilon))$ and lower bounded by $\Omega(n^2 \cdot~\log (1/\varepsilon))$. If one endpoint of the chain remains stationary, this result can be extended to the non-collinear case. If both endpoints move, we identify a family of instances whose runtime is unbounded. For the continuous model, we give a strategy with an optimal runtime bound of $\Theta(n)$. Avoiding an unbounded runtime similar to the discrete case relies crucially on a counter-intuitive aspect of the strategy: slowing down the endpoints while all other robots move at full speed. Surprisingly, we can show that a similar trick does not work in the discrete model.

Methodenentwicklung zur Schädigungsmodellierung für die numerische Prozesssimulation mechanischer Fügeverfahren - Otroshi, Mortaza; Meschut, Gerson
Der Karosseriebau ist zunehmend durch die Verwendung unterschiedlicher Werkstoffe in Mischbauweise gekennzeichnet, was zu einem Einsatz von mechanischen Fügeverfahren geführt hat. Hieraus resultieren die Zielsetzungen, die mechanischen Fügeverfahren in ihrer Effizienz und ihren Einsatzbereichen zu erweitern, sowie die Anzahl der Experimente zu reduzieren und Entwicklungszyklen zu verkürzen. Dies erfolgt mit Unterstützung der numerischen Simulation. Neben der Beschreibung des plastischen Verhaltens gilt es auch, das Schädigungsverhalten abzubilden. Der Fügeprozess bzw. die Fügerichtung erfolgt senkrecht zur Blechoberfläche und führt somit zu einem dreidimensionalen Zustand der Fügelemente. Hieraus leitet sich die Herausforderung ab, das Werkstoffversagen in Abhängigkeit der Beanspruchungssituation zu beschreiben. Ein einfacher Ansatz zur Abbildung des Durchdringens ist ein geometrisches Trennkriterium. Ein solches Kriterium basiert i.d.R. auf einem experimentell beobachteten Verhalten und ist somit nicht prognosefähig für Variationen bzgl. Werkzeugkonfigurationen, Blechdicken- und Werkstoffgüten-Kombinationen. In diesem Projekt wird das Schädigungsmodell GISSMO (Generalized Incremental Stress State dependent damage Model) verwendet, um die Entwicklung der duktilen Schädigung zu beschreiben und den Bruchbeginn während des Stanzniet- und Schneidclinchens vorherzusagen. Der Spannungszustand während der Prozesssimulation wird untersucht und die verschiedenen Schädigungsproben werden experimentell erprobt, um die Versagenskurven zu charakterisieren. Die Versagenskurven werden im Schädigungsmodell GISSMO definiert. Um die Genauigkeit des Modells zu gewährleisten, wird die Verifizierung des Modells durch die Simulation von Schädigungsproben mit dem Schädigungsmodell durchgeführt. Zur Validierung des Modells wird die Simulation des Fügeprozesses mit dem Schädigungsmodell durchgeführt und die Ergebnisse von Simulation und Experiment verglichen. Darüber hinaus werden Sensitivitätsanalysen durchgeführt, um die Einflüsse der Fertigungsprozesse, der Lackierung und des Diskretisierungsgrades auf das Schädigungsverhalten des Materials zu identifizieren. Das IGF-Vorhaben „Methodenentwicklung zur Schädigungsmodellierung für die numerische Prozesssimulation mechanischer Fügeverfahren" der Forschungsvereinigung EFB e.V. wurde unter der Fördernummer AiF 19452N über die Arbeitsgemeinschaft industrieller Forschungsvereinigungen (AiF) im Rahmen des Programms zur Förderung der Industriellen Gemeinschaftsforschung (IGF) vom Bundesministerium für Wirtschaft und Energie aufgrund eines Beschlusses des Deutschen Bundestages gefördert. Der Abschlussbericht ist als EFB-Forschungsbericht Nr. 527 erschienen und bei der EFB-Geschäftsstelle und im Buchhandel erhältlich.

"Solange dieser Mann gut Deutsch sprechen kann, ist auch kein Problem...": Evaluative Reaktionen auf einen L2-Akzent aus Sicht von Sprecher*innen - Müller, Mareike; Settinieri, Julia (Fremdsprachen Lehren und Lernen)
This article investigates learners’ accounts of and reactions to interlocutors’ evaluations of their L2 pronunciation. Previous studies demonstrate both the pervasiveness of social evaluation processes in native and non-native speaker interactions and the impact of learners’ beliefs about pronunciation on their learning and communicative behavior. Adding to these strands of research, this project sheds light on how learners perceive evaluative reactions to their accents by native speakers and the relationship between such evaluations and learners’ reported evaluative, emotional and behavioral responses. The study draws on 8 international students at a German university. The data were collected in semi-structured interviews and analyzed within the framework of qualitative content analysis. The results give insight into conditions and strategies that may support learners in establishing constructive interpretations of the effects of their accents on their social acceptance.

School-based interventions to support student participation. A comparison of different programs. Results from the FRIEND-SHIP project - Hassani, Sepideh; Aroni, Katerina; Schwab, Susanne; Resch, Katharina; Toulia, Anastasia; Alves, Silvia; Görel, Gamze; Löper, Marwin Felix; Avramidis, Elias; Silveira- Maia, Mónica; Sanches-Ferreira, Manuela; Hellmich, Frank

Simulationsbasierte Betriebsfestigkeitsanalyse stanzgenieteter Bauteile - Otroshi, Mortaza; Meschut, Gerson; Masendorf, Lukas; Esderts, Alfons
In modern lightweight designs, it is important to find a compromise between the strength and the weight of the construction detail. Hence, hybrid structures made of aluminum and steel materials are increasingly being used in automotive applications. Due to limitations in the quality of resistance spot welding, self-piercing riveting can be used as an alternative process to join sheets from different material groups. The aim of this project is to develop a computational method to assess the self-piercing riveted components subjected to the cyclic loads. To achieve this goal, two approaches are followed: Evaluation unsing internal forces: A substitute model is developed to describe the stiffness of self-piercing riveted joints subjected to different loading conditions. The parameters of the substitute model are identified and the internal force components acting on the joint are evaluated. The model provides the basis for the subsequent fatigue life estimation of self-piercing riveted components. For joints subjected to low bending moments, the fatigue life of components can be estimated accurately. Due to lack of specimen geometries producing pure bending and the combination of tension-bending forces, it is not possible to estimate the fatigue life of complex components subjected to high bending moments. Based on the results of [Mesc 16], the methodology is further developed to determine the stresses acting on the joint and to characterize the joining point with the use of simulations. The local concept proposed in the FKM guideline nonlinear provides the basis for the analytical assessment of self-piercing riveted components. In this regard, the cyclic behavior of the material and the local stresses are required as input data. The cyclic behavior of the aluminum EN AW-6181A-T6 and steel HX340LAD sheets were already determined in the previous project. Subsequently, in this project the properties of the rivet made of 38B2 steel are identified. The finite element analysis using elastic-plastic material behavior is used to determine the stresses in the joint subjected to the cyclic loads. To verify the model, the results of simulations and experiments are compared concerning the crack initiation zone as well as the determined number of cycles. To determine the stresses that can be used for the analytical assessment, the damage relevant load components need to be identified. In this regard, it is recommended to use the normal stress perpendicular to the crack propagation direction, the stress of crack opening mode I. Using the damage parameter PRAM and considering the support factors according to the FKM guideline nonlinear, a reliable estimation of the crack initiation zone within the joint is possible. Regarding the joint made of aluminum sheet EN AW-6181A, the methodology is able to provide promising results. However, regarding the joints made of aluminum EN AW-6181A and steel HX340LAD sheets, there is still potential to improve the results. The reasons for this are described in chapter 7.2.5 and 7.2.6. An analytical fatigue assessment is relatively easy to achieve with procedure 1. However, contrary to the objective formulated above, expensive fatigue tests are necessary to determine the failure conditions (strength values). This disadvantage can be circumvented by determining the strength information of individual joining points under different load types using procedure 2. The latter, in return, is not suitable for the assessment of complex components with several joining points. Due to the increasing calculation times of the simulation, the application in this case is not economically reasonable. By the described combination of method 1 and 2, the disadvantages of the two individual concepts can be compensated. An analytical fatigue assessment of self-piercing riveted components can be carried out based on the cyclic material behavior. The objective of the project was achieved.

Country-by-Country Reporting Goes Public - Cui Bono? - Lagarden, Martin; Schreiber, Ulrich; Simons, Dirk; Sureth-Sloane, Caren (International Transfer Pricing Journal)
After the introduction of CbCR – pursuant to the BEPS Project (Action 13) in 2015 –, which was established to reduce the information asymmetry between MNEs and tax authorities of the countries they operate in, now public CbCR – as suggested by the EU Commission in 2016 – is discussed as a next step. Here, the objective is to overcome information asymmetries between MNEs and the general public of the countries they operate in. Starting from the assumption that regulators care about the legitimacy of tax laws, this article evaluates pros and cons of public CbCR. The authors find that from the perspective of information asymmetries, public CbCR increases tax transparency only marginally at best. Accordingly, it is concluded that democracies that are based on the rule of law seem to rely on pillories in terms of public CbCR to enforce fair tax payments.

Data Science und Big Data in der beruflichen Bildung – Konzeption und Erprobung eines Projektkurses für die Sekundarstufe II - Opel, Simone Anna; Schlichtig, Michael (Sammelband der 27. Fachtagung der BAG Berufliche Bildung)
Die Themen „Big Data“, „Künstliche Intelligenz und „Data Science“ werden seit einiger Zeit nicht nur in der breiten Öffentlichkeit kontrovers diskutiert, sondern stellen für die Ausbildung in den IT- und IT-nahen Berufen schon heute neue Herausforderungen dar, die in Zukunft durch die gesellschaftliche und technologische Weiterentwicklung hin zu einer Datengesellschaft noch größer werden. An dieser Stelle stellt sich die Frage, welche Aspekte dieses großen Themenkomplexes für Schule und Ausbildung von Wichtigkeit sind und wie diese Themen sinnstiftend und gewinnbringend in die informatische Ausbildung in verschiedenen Bildungsgängen integriert werden können. Im Rahmen des von uns im Jahr 2017 organisierten Symposiums zum Thema „Data Science“ wurden für die Bildung relevante Aspekte erörtert, wodurch als Kernelemente für den Unterricht Algorithmen der Künstlichen Intelligenz und ihre Anwendung in Industrie und Gesellschaft, Explorationen von Big Data sowie der Umgang mit eigenen Daten in sozialen Netzwerken herausgearbeitet wurden. Ziel ist, aus diesen Themenbereichen sowohl ein umfassendes Curriculum als auch Module für verschiedene Unterrichtsszenarien zu entwickeln und zu erproben. Durch diese Materialien soll es Lehrkräften aus der Informatik, Mathematik oder Technik ermöglicht werden, diese Themen auf Basis des Curriculums und der erprobten Unterrichtskonzepte selbst zu unterrichten. Hierfür wurde im Rahmen des Projekts ProDaBi (Projekt Data Science und Big Data in der Schule, https://www.prodabi.de), initiiert von der Telekom Stiftung, ein experimenteller Projektkurs entwickelt, den wir mit Schüler:innen der Sekundarstufe II an der Universität Paderborn im Schuljahr 2018/19 durchführten. Dieser Kurs enthält neben einem Modul zur Exploration von Big Data und einem weiteren Modul zum Maschinellen Lernen als Teil der Künstlichen Intelligenz auch eine Projektphase, die es in Zusammenarbeit mit lokalen Unternehmen den Schüler:innen ermöglicht, das Erlernte in ein reales Data Science-Projekt einzubringen. Aus den Erfahrungen dieses Projektkurses sowie den parallel durchgeführten Erprobungen einzelner Bausteine auch mit beruflichen Schulen werden ab dem Schuljahr 2019/20 die hierfür verwendeten Materialien weiterentwickelt und weiteren Kooperationspartnern zur Erprobung zur Verfügung gestellt. Damit wurden zum Ende des Projekts nicht nur vollständige Unterrichtsmaterialien, sondern auch ein umfassendes Curriculum entwickelt.
Keywords: Berufsbildung; vocational education; Ausbildung; training; berufliche Weiterbildung; advanced vocational education; Digitalisierung; digitalization; Unterricht; teaching; Lehrmethode; teaching method; Interdisziplinarität; interdisciplinarity; Fachdidaktik; subject didactics; Curriculum; curriculum; gewerblich-technischer Beruf; vocational/technical occupation; Fachkraft; specialist; Qualifikationsanforderungen; qualification requirements; Kompetenz; competence; Lehrerbildung; teacher training; Bundesrepublik Deutschland; Federal Republic of Germany

Learning Open Science by doing Open Science. A reflection of a qualitative research project-based seminar - Steinhardt, Isabel (Education for Information)
Openness in science and education is increasing in importance within the digital knowledge society. So far, less attention has been paid to teaching Open Science in bachelor’s degrees or in qualitative methods. Therefore, the aim of this article is to use a seminar example to explore what Open Science practices can be taught in qualitative research and how digital tools can be involved. The seminar focused on the following practices: Open data practices, the practice of using the free and open source tool “Collaborative online Interpretation, the practice of participating, cooperating, collaborating and contributing through participatory technologies and in social (based) networks. To learn Open Science practices, the students were involved in a qualitative research project about “Use of digital technologies for the study and habitus of students”. The study shows the practices of Open Data are easy to teach, whereas the use of free and open source tools and participatory technologies for collaboration, participation, cooperation and contribution is more difficult. In addition, a cultural shift would have to take place within German universities to promote Open Science practices in general.
Keywords: Open Science; Open Education Practices; Library and Information Sciences; Education; Information Systems

Anforderungen an Studienordnungen in einer digital vernetzten Welt - Caruso, Carina; Martin, Alexander (Zeitschrift für Hochschulentwicklung)
Der Beitrag widmet sich der Frage, wie lehrer*innenbildende Hochschulen der Digitalisierung auf der Ebene der Überarbeitung und Anpassung von Studienordnungen begegnen können. Ziel des interdisziplinären Vorhabens ist es, ausgehend von einer Inhaltsanalyse nordrhein-westfälischer Studienordnungen einen Kriterien- bzw. Fragenkatalog zu entwickeln, der diejenigen bildungspolitischen Vorgaben zur Verankerung digitaler Kompetenz fasst, die künftigen Akkreditierungen von Studiengängen zugrunde liegen werden und der fach- und standortübergreifend eingesetzt werden kann.
Keywords: Studienordnungen; Digitalisierung; Lehrer*innenbildung; Professionalisierung / study regulations; digitalisation; teacher training; professionalisation

Project “Schule für alle” as a mentoring programme in university teacher education: Professionalization processes of student teachers in different practical university phases - Kottmann, Brigitte; Pieper, Catania (Hungarian Educational Research Journal)
In the mentoring programme project “Schule für alle” (“School for all”) at the University of Bielefeld in North Rhine-Westphalia, university students of primary or special education support a child who is in a situation of crisis for more than one year. In addition, the university students receive ongoing, systematic university support (cf. Kottmann, 2007, p. 32; Kottmann, 2014, p. 380). The accompanying research by “Schule für alle” focuses on the professionalization processes of student teachers during practical phases at universities; accordingly, control groups were included on a pro rata basis. In the pre-post design, all students completed a questionnaire (cf. Pieper, Kottmann & Miller, 2018, p. 294), the evaluation of which shows few changes in the professional perception of competence. Students of the mentoring programme also regularly reflected on their practical experience. Based on the objective hermeneutics it was discovered that the conception of the project supports the process of perceiving, acknowledging and becoming more sensitive in regard to heterogeneous realities in life (cf. Pieper & Kottmann 2019b, p. 312) and that students can consciously perceive and reflect their own normative expectations (cf. Pieper & Kottmann 2019a, p. 79). The article primarily presents the results of the pre-post survey in detail and adds insights into the qualitative evaluation processes. In the conclusion, the potential of the project and mentoring programmes in general, specifically for teacher training students, is described.
Keywords: professionalization of teacher training students; practical university phases; teacher training at universities; men-toring programmes

A modular, scalable open-hardware platform for project-based laboratory courses in electrical engineering studies - Hetkämper, Tim; Krumme, Matthias; Dreiling, Dmitrij; Claes, Leander (SEFI 48th Annual Conference Proceedings - Engaging Engineering Education)

Lebenswelten und soziale Netzwerke von jungen Geflüchteten und Zugewanderten am Übergang in Ausbildung und Beruf. - Heisler, Dietmar; Schemmer, Susanne (BWP@ Berufs- und Wirtschaftspädagogik - online)
Jugend wird als eine eigenständige Lebens- und Entwicklungsphase betrachtet. Für junge Geflüchtete stellt sie eine besondere Herausforderung dar. Für sie geht es nicht nur um die Bewältigung alterstypischer Entwicklungsaufgaben, sondern auch um eine gelingende Integration in die Aufnahmegesellschaft. Dazu gehören u. a. das Kennenlernen und die Aneignung von Sprache, Kultur und Werten, genauso die Erschließung von Alltagsräumen und Lebenswelten, z. B. von Freizeitmöglichkeiten, Bildung und von beruflichen Erfahrungsräumen. Die Frage zur gelingenden Integration und Gestaltung von Lebenswelten junger Geflüchteter wurde im Kontext der wissenschaftlichen Begleitung des Projekts „angekommen in Deiner Stadt“ der Walter Blüchert Stiftung genauer untersucht. Der Beitrag referiert u. a. die Ergebnisse einer in diesem Kontext durchgeführten egozentrierten Netzwerkanalyse. Die Ergebnisse zeigen, dass die Angebote den Rahmen für den Aufbau und die Erweiterung kommunikativer, sozialer Netzwerke darstellen und lebensweltliche Zugänge öffnen.
Keywords: Jugend; Lebensweltorientierung; soziale Netzwerke; geflüchtete Jugendliche; Lebenslagen junger Geflüchteter und Zugewanderter

Productivity optimization through project matching - N., N.

Video analysis in Design-Based Research – Findings of a project on self-organised learning at a vocational school - Gössling, Bernd; Daniel, Desiree (EDeR. Educational Design Research)
The use of video analysis in Design-Based Research (DBR) seems to be promising, because the quality of video data matches the reality of educational fields. Educational fields are multidimensional and complex. And more than other types of data, video may capture, for example, the simultaneity of verbal and non-verbal interactions. This seems to be valuable in the quest for new insights and better designs of educational interventions. However, to date there has been limited use of video data in researching their design. This paper aims at reflecting how the benefits of video-based analysis may be utilised in DBR. Experiences with the collection and analysis of video data in a project to design self-organised learning (SOL) at a vocational school in Germany will be used as a case study to illustrate the type of findings that may feed into the DBR process. In this case, the project school had already introduced a sophisticated SOL model but was experiencing various implementation difficulties. Resolving issues like this requires insights into how exactly a concept is realised and what happens in the field. Therefore, video data on classroom interactions was gathered and sub-sequently analysed using the documentary method. This led to the reconstruction of two different types of orientation that were guiding the students when they dealt with their self-organised learning environment. In a subversive orientation, students playfully infiltrate the formal learning space with peer activities. In a confirming orientation, students stick to both, the (informal) rules of the (formal) learning arrangement and of the peer environment, thus expressing respect for the boundary between these two worlds. These findings have been used to redesign the SOL intervention.
Keywords: Pulmonary and Respiratory Medicine; Pediatrics; Perinatology and Child Health

Erhebung, Transformation und Präsentation digitaler Forschungsdaten - Ried, Dennis (Brückenschläge zwischen Musikwissenschaft und Informatik. Theoretische und praktische Aspekte der Kooperation)
The process of data acquisition and transformation of Baumann Digital and Joachim-Raff-Archiv is the subject of this poster description. The data in both projects is (meanwhile) based on TEI and MEI to obtain a machine-readable corpus. The presentation platform created for this project was initially intended as a simple form of visualization for internal use, i. e. for structuring, proofreading of digital contents and first evaluations. The xQuery-based application for eXist-db was developed in detail during the first period of the Baumann Digital project, adding the dimension of public presentation to its original purpose. This poster focuses on the process of collecting, transforming and presenting the data of these two small projects, which have different research interests but deal with similar archival material.